Systems and methods for retaining nanoparticles within fibrous materials

By using sprayers and fibrosis devices in fiber filters to deeply penetrate the fiber substrate, the problem of low efficiency and short life of fiber filters to capture submicron particles is solved, achieving more efficient filtration performance and longer Service life.

CN119278082APending Publication Date: 2025-01-07MATIF LUXEMBOURG +1
View PDF 18 Cites 0 Cited by

Patent Information

Application Number
CN202380041728.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-04-08
Filing Date
2023-04-07
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

Existing fiber filters are inefficient and have short lifetimes in capturing submicron particles, and it is difficult to evenly distribute nanoparticles in nonwoven materials, resulting in a degradation of filtration performance.

Method used

The nanoparticles are used to penetrate deep into the fiber substrate through the sprayer, and the adhesive is used to promote the bonding of the nanoparticles to the fiber to ensure their uniform distribution. The nanoparticles are dispersed to the depths of the fiber material through the sprayer and fibrosis device. , enhance filtration efficiency and dust capacity.

Benefits of technology

It improves the filtration efficiency of fiber materials, extends the service life of the filter, enhances the capture ability of submicron particles, and reduces pressure loss.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119278082A_ABST
    Figure CN119278082A_ABST
Patent Text Reader

Abstract

Systems, devices, and methods are provided for producing a product, such as a filter, comprising fibrous material. A system for producing a fibrous material includes a feeder for advancing a fibrous substrate from an upstream end to a downstream end and a first dispersing device for dispersing a binder onto the substrate to coat at least a portion of the fibers with the binder. The system also includes a second dispersion device for dispersing the nanoparticles through the first surface of the substrate such that the nanoparticles are disposed between the first surface and the second surface of the substrate. The binder promotes adhesion between the fibers and the nanoparticles, thereby retaining the nanoparticles in the internal structure of the substrate. Furthermore, facilitating such adhesion provides a more uniform distribution of the nanoparticles throughout the substrate, thereby improving the performance characteristics of the material.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application claims the benefit of U.S. Provisional Application Serial No. 63 / 329,155, filed April 8, 2022, the entire disclosure of which is incorporated herein by reference for all purposes. This application is also related to commonly assigned, co-pending U.S. Provisional Patent Application Serial Nos. 63 / 329,009, 63 / 328,983, 63 / 328,998, 63 / 328,970, 63 / 328,959, 63 / 329,018, 63 / 329,137, 63 / 329,146, 63 / 329,158, 63 / 329,161, and 63 / 329,162, all of which were filed on April 8, 2022, the entire disclosures of which are incorporated herein by reference in their entirety for all purposes. Technical Field

[0003] The present description relates generally to systems and methods for making fibrous materials and products containing fibrous materials, and more particularly, to systems and methods for retaining nanoparticles within fibrous materials. Background Art

[0004] Because of their fine fiber size, fibrous materials are particularly useful for capturing contaminants in filtration devices. The fibers of filter media are measured in microns and are formed by spunbonding, meltblowing, electrospinning or other techniques. As fluid flows through the filter media, the fine fibers capture and retain contaminants within.

[0005] The two main types of filtration devices that incorporate fibrous materials include surface filters and depth filters. Surface filters (such as membranes or films) act as a barrier to capture contaminants before they enter the media structure. These surface filters typically have sub-micron pore sizes and narrow pore size distributions. Surface filters tend to have relatively high particle capture efficiencies. However, they also have relatively high pressure drops and low dust holding capacities. High pressure drops result in reduced air flow through the filter. Low dust holding capacities significantly reduce the life of the filter. As a result, surface filters have a limited number of applications in the air filtration industry.

[0006] Depth filters are commonly used in air filtration units with medium to high efficiency, low pressure drop, and relatively high dust holding capacity. Traditional residential and commercial air filters, such as HEPA filters, are generally rated based on the filter's ability to capture particles ranging from approximately 0.3 to 10 microns. This rating is called the Minimum Efficiency Reporting Value, or MERV, and is established by the American Society of Heating, Refrigerating and Air-Conditioning Engineers (ASHRAE). MERV ratings range from 1-16, with higher values ​​indicating greater efficiency in capturing specific types of particles.

[0007] Pollutants come in a wide range of sizes. However, pollutants smaller than 1 micron are the most harmful particles to the human body and are relatively difficult to filter. For example, traditional mechanical air filters typically report a MERV rating of about 8-10 for fiber filter materials. Therefore, these filter media typically do not capture submicron particles, such as viruses and other harmful pathogens.

[0008] The filtration industry has focused on two different methods of capturing these submicron particles: electrostatic forces and utilizing nanoparticles in the filter media. Electrostatic filters are formed by electrostatically charging the fibers within a fibrous material using triboelectric methods, corona discharge, hydrocharging, electrospinning, or other known methods. Electrostatic filters are most effective at capturing submicron particles, fairly effective at capturing particles between 1 and 3 microns, and least effective at capturing larger particles between 3 and 10 microns. Electrostatic fibers are commonly used in many filtration applications, such as face masks and HEPA filters, to filter submicron contaminants, such as viruses, etc.

[0009] One disadvantage of electrostatic filters is that the electrostatic charge decays over time and with filter use. As a result, the filter's efficiency decreases relatively quickly, shortening its life. For example, an electrostatic filter with an initial MERV rating of 13 may lose at least 2-3 MERV rating points after the electrostatic force decays. This compromises the integrity of the filter and may partially or completely inhibit its ability to capture submicron particles.

[0010] Another approach to capturing submicron contaminants is to use nanoparticles in combination with fibers. A filtration system may employ a filter media that includes relatively large fibers with diameters measured in microns and relatively small nanoparticles. The nanoparticles increase the surface area within the media for capturing particles by reducing the overall fiber size within the media. The nanoparticles also tend to collapse onto each other, increasing the packing density within the filter media. It has been shown that even a small number of nanometer-sized fibers in a layer formed on a microfiber material can improve the filtration characteristics of the material.

[0011] The most common method of incorporating nanoparticles into filter media is to apply a thin layer of continuous nanofibers to a non-manufactured substrate by electrospinning. The nanoparticles typically extend parallel or perpendicular to the surface of the bulk filter media layer, providing high efficiency filtration of small particles in addition to the filtration of larger particles provided by the coarse filter media. For example, U.S. Patent No. 6,743,273 discloses a filter media in which a continuous nanofiber layer is deposited on the surface of a substrate. U.S. Patent No. 10,799,820 also discloses an air filter media comprising a continuous nanofiber layer on the surface of the filter media.

[0012] While existing filter media incorporating nanoparticles have improved the relative efficiency of these filters, the commercial potential of these filters in certain applications is limited because the nanoparticles are typically dispersed on the surface of the nonwoven material. The relatively thin layer of nanoparticles on the filter surface provides only limited particle filtration and has a relatively low dust holding capacity.

[0013] Although many attempts have been made to incorporate nanomaterials into filter media to improve overall filtration efficiency, these attempts have been limited to so-called "wetlaid" methods. These wetlaid methods involve incorporating short-cut nanofibers into a liquid slurry to separate entangled nanofibers with the aid of a surfactant. For example, U.S. Patent No. 10,252,201 discloses a filter medium made of a mixture of short-cut nanofibers and short-cut coarse fibers formed by a wet-laid method. Similarly, U.S. Patent Application No. 2021 / 0023813 discloses a method for producing a composite structure consisting of a continuous fiber nonwoven substrate and discontinuous fibers (e.g., carbon nanofibers). The method includes pulling a continuous fiber nonwoven substrate through a slurry of discontinuous fibers, wherein the nanomaterial is embedded in the nonwoven substrate.

[0014] While these structures have shown increased efficiency, they also suffer from other issues such as reduced life and / or efficiency when the media is placed under normal use conditions. Additionally, these wet-laid methods have not been successful in incorporating the nanoparticles uniformly throughout the nonwoven material, which results in agglomeration of the nanoparticles within the material, further reducing its efficiency and overall dust holding capacity.

[0015] Therefore, there is a need for improved systems and methods for producing products (such as filters) containing fibrous materials. It is particularly desirable to incorporate and retain nanoparticles throughout the fibrous material to improve the performance characteristics of the filter. Summary of the invention

[0016] A brief overview of the claimed subject matter is presented below to provide a basic understanding of some aspects of the claimed subject matter. This summary is not a comprehensive overview of the claimed subject matter. It is neither intended to identify the key or important elements of the claimed subject matter nor to describe the scope of the claimed subject matter. Its sole purpose is to present some concepts of the claimed subject matter in a simplified form as a prelude to the more detailed description presented later.

[0017] Systems, devices and methods for producing fibrous materials and products containing fibrous materials are provided. The fibrous material can include a substrate, such as a sheet, layer, film, apertured film, net, mesh or other medium. The substrate contains fibers and includes nanoparticles incorporated into and retained within at least a portion of the substrate.

[0018] In one aspect, a system for producing a fibrous material comprises a feeder for advancing a fibrous substrate from an upstream end to a downstream end and a first dispersing device for dispersing an adhesive onto the substrate to cover at least a portion of the fibers with the adhesive. The system also includes a second dispersing device for dispersing nanoparticles across a first surface of the substrate so that the nanoparticles are arranged between the first surface and the second surface of the substrate. The adhesive promotes bonding between the fibers and the nanoparticles, thereby retaining the nanoparticles in the internal structure of the substrate. In addition, promoting this bonding provides a more uniform distribution of the nanoparticles throughout the substrate, thereby improving the performance characteristics of the material. For example, in filter applications, a more uniform distribution of nanoparticles improves the efficiency of the filter media while reducing pressure loss.

[0019] Adhesive can be dispersed using nozzle, dip coating, ultrasonic spray coating, dip coating, spin coating, gravure coating, touch roller coating, screen coating, powder coating, static electricity, sputter coating or similar coating technology.In one embodiment, the first dispersing device comprises a spray coater, which is configured to "go deep" into the internal structure of substrate with adhesive.As used herein, the term "depth / go deep / depth (in depth)" means that adhesive exceeds the first surface dispersion of substrate, so that at least some adhesives are arranged between the first surface and the second relative surface in substrate or medium internal structure.This helps nanoparticles to remain in the depths inside the substrate.

[0020] In certain embodiments, adhesive and / or nanoparticle are dispersed throughout the substantially whole medium from the first surface to the relative second surface.In other embodiments, adhesive and / or nanoparticle are dispersed to the position between the first surface and the second surface by the part of medium from the first surface.In other embodiments, adhesive and / or nanoparticle are arranged from the first surface of base material to the relative second surface with density gradient.The density of adhesive and / or nanoparticle can be larger at the first surface or the second surface place.

[0021] In certain embodiments, the products are filter media and filters, such as air filters, masks, gas turbine and compressor intake filters, and panel filters, etc. The nanoparticles increase the total surface area within the filter media, which increases its filtration efficiency and allows the capture of submicron pollutants without significantly compromising other factors, such as the pressure drop (i.e., air flow) through the filter. In addition, the filters produced using the systems and methods described herein are able to withstand rigorous conditioning, which allows the filter to achieve the same level of filtration performance throughout its service life.

[0022] The amount of adhesive dispersed into the substrate can be controlled by adjusting the nozzle size of the sprayer or controlling the flow rate of the adhesive through the nozzle. In one embodiment, the nozzle contains one or more openings configured to form the adhesive into droplets having a size of about 20 to 30 microns.

[0023] The adhesive can comprise various conventional materials, including natural base materials, such as starch, dextrin or guar gum, etc., or synthetic resins, such as EVA, PVA, PVOH, SBR, polyglycolide and combinations thereof. In certain embodiments, solvent-based adhesives are used, wherein bonding occurs when the solvent evaporates. The adhesive or bonding material is preferably present in relatively small amounts to bond a single nanoparticle to the fibers of the entire substrate.

[0024] In a preferred embodiment, the adhesive or adhesive material comprises dextrin. In yet another embodiment, the adhesive comprises a composition of various substances (e.g., water, 2-hexyloxyethanol, isopropanolamine, sodium dodecylbenzene sulfonate, lauramine oxide, and ammonium hydroxide). In yet another embodiment, the adhesive comprises at least PVOH. The adhesive can be a solution, emulsion, suspension, hot melt, curable, neat, and / or a combination.

[0025] In some embodiments, the system also includes an energy source for crosslinking adhesive. Adhesive can be, for example, included in an adhesive resin that is crosslinked after coating adhesive on substrate. Adhesion (water resistance / solvent resistance) can be promoted by self-crosslinking during solvent evaporation in adhesive formulations or thermal activation in drying process. For some adhesives, the energy source can include an electromagnetic radiation source of high energy wavelength, including but not limited to RF, UV or electron beam.

[0026] In some embodiments, the adhesive or adhesive material may include a surfactant to reduce the surface or interfacial tension of the adhesive, thereby increasing its dispersibility and wettability, and making it easier for the adhesive to penetrate deep into the substrate. Suitable surfactants for use with the adhesive disclosed herein include nonionic surfactants, anionic surfactants, cationic surfactants, and amphoteric surfactants, such as sodium stearate, 4-(5-dodecyl)benzenesulfonate, sodium dodecylbenzenesulfonate wetting agents, docusate (dioctyl sodium sulfosuccinate), alkyl ether phosphates, benzalkonium chloride (BAC), and perfluorooctane sulfonate (PFOS), etc.

[0027] In some embodiments, the sprayer is located upstream of the nanoparticle dispersing device so that the binder is sprayed into the substrate before the nanoparticles are deposited. In other embodiments, the sprayer is located downstream of the nanoparticle dispersing device so that the binder is sprayed after the nanoparticles are deposited. In other embodiments, the system may include two sprayers; one located upstream of the nanoparticle dispersing device and a second sprayer located downstream to coat the substrate with a second binder after the nanoparticles are deposited.

[0028] In some embodiments, each sprayer has more than one nozzle head. For example, the nozzle heads can be arranged in series to obtain better uniformity or increase the fiber spray width. Optionally, the nozzle heads can be placed side by side, i.e., across the width of the substrate to ensure that the adhesive is applied over the entire width of the substrate.

[0029] In a preferred embodiment, a negative pressure source or vacuum source (not shown) is arranged below the substrate, opposite to the sprayer, to increase the penetration depth and uniformity of the adhesive. The negative pressure source can be any suitable suction device that sucks the adhesive through the substrate, such as a suction pump, etc.

[0030] The system may further comprise a heating and / or drying device downstream of the nozzle to promote bonding between the fibers and the nanoparticles.

[0031] In certain embodiments, the fibrous material (i.e., fibers and / or nanoparticles) can be electrostatically charged so that, for example, contaminants can be captured by mechanical and electrostatic filtration. The bonding between fibers and nanoparticles can also be enhanced by electrostatically charging the nanoparticles, fibers, or both.

[0032] In certain embodiments, the system also includes a fiberizing device, which is coupled to a second dispersing device, for separating and / or isolating nanoparticles from nanofiber groups or bundles in a fluid medium, and then dispersing the nanoparticles on a substrate to form a product containing fibers and nanoparticles. As used herein, the term "fiberizing" means that nanoparticle clusters, bundles or other groups are converted (for example, opened, separated, isolated and / or individualized) into at least one single nanoparticle having a size less than 1 micron. In certain embodiments, nanoparticles can be separated or isolated in any suitable gaseous medium (for example, air, helium, nitrogen, oxygen and carbon dioxide, etc.), and are dispersed into products, substrates or fiber streams by airflow, aerosol, evaporator, spray or other suitable conveying mechanisms. Separate and / or isolate single nanoparticles in a gaseous medium, and then disperse them in substrates or airflows so that nanoparticles are more evenly distributed throughout the product.

[0033] In one particular aspect, the fiberizing device comprises a gas source (e.g., compressed air or other suitable gas) and a pump for pulling the nanofiber group from the separator through the channel into the device. The compressed air source provides a motive fluid to circulate the nanofibers throughout the fiberizing device and ultimately outward into the nozzle. The pump may include any suitable pump, such as a positive-displacement pump, a centrifugal pump, and an axial flow pump, etc. In one embodiment, the pump comprises an ejector, which is configured to generate enough negative pressure to draw the nanofiber group out of the separator and into the pump through the channel.

[0034] The system may also include an energy source, such as a second pump or a second ejector, etc., coupled to the first ejector and configured to push the nanofibers from the first ejector toward a surface at a sufficient velocity to break up the nanofibers and convert at least some of the nanofiber groups into individual nanoparticles. Applicants have found that pushing the nanofibers toward a suitable surface at a velocity of about 500 feet per minute (fpm) to about 10,000 fpm, preferably about 2,000 fpm to about 6,000 fpm, is sufficient to break up at least some of the nanofibers into individual nanoparticles.

[0035] The surface can be any surface that hinders the nanofibers from flowing through the channel, such as the inner wall of the channel at the connection point, or other changes in the direction of the inner wall, such as a curved surface or a vertical surface, etc. Optionally, the channel can include a wall or other surface arranged in the channel or protruding into the channel in the fluid path. In one embodiment, the channel extends to a roughly T-shaped joint, which includes two independent channels extending from the joint. The second ejector is configured to push the nanofibers into the wall of the T-joint at a speed sufficient to separate at least some of the nanofibers.

[0036] In some embodiments, the fiberizing device further comprises one or more reactors for separating individual nanoparticles that have been isolated from the nanofiber group that has not been completely broken up. The reactor comprises a housing coupled to the channel and having an inner cavity and a negative pressure source, the negative pressure source being configured to suck the nanofiber group away from the individual nanoparticles.

[0037] In embodiments, the reactors each comprise a rod or tube extending through the lumen and one or more inlets located at one end of the lumen and substantially surrounding the tube, and in some embodiments, the inlet may substantially extend through the center of the lumen. The inlet is coupled to the passage so that the nanofiber clusters and individual nanoparticles are sucked into the chamber through the inlet. The center tube comprises an opening at the end opposite to the inlet. The opening is coupled to the internal passage in the tube and has an outlet coupled to a nozzle or other dispersing device. This allows the nanoparticles to enter the reactor through the inlet, then enter the tube and enter the dispersing device.

[0038] Reactor can also comprise one or more outlets at the opposite end of inlet.The larger and heavier nanofiber clusters that have not yet been broken are sucked out through these outlets.Therefore, the nanoparticles of isolation and individualization are sucked into the nozzle, and the nanofiber clusters are sucked out through the outlet.These outlets can be coupled to the first pump or the second pump, or coupled to the other pump in the fiberizing device, and these pumps are designed to further break up the nanofiber clusters and recirculate them back to the reactor.

[0039] In another aspect, a method for producing a fibrous material includes providing a fibrous substrate having a first surface and a second surface opposite the first surface, and coating the substrate with a binder. The nanoparticles are dispersed through the first surface of the substrate such that the nanoparticles are retained at least between the first surface of the substrate and the second surface opposite the first surface. The binder promotes bonding between the nanoparticles and the fibers, ensuring that they are substantially evenly distributed throughout the internal structure of the substrate.

[0040] In an embodiment, the adhesive is sprayed onto the substrate so that the adhesive penetrates the first surface of the substrate to its internal structure. In certain embodiments, negative pressure is applied to a second surface of the substrate opposite the first surface to enhance penetration of the adhesive therethrough.

[0041] In certain embodiments, adhesive and / or nanoparticle are dispersed throughout the substantially whole medium from the first surface to the relative second surface.In other embodiments, adhesive and / or nanoparticle are dispersed to the position between the first surface and the second surface by the part of medium from the first surface.In other embodiments, adhesive and / or nanoparticle are arranged from the first surface of base material to the relative second surface with density gradient.The density of adhesive and / or nanoparticle can be larger at the first surface or the second surface place.

[0042] In certain embodiments, the volume of adhesive sprayed onto the substrate is controlled to ensure that an optimal amount of adhesive is present throughout the substrate to retain the nanofibers. In one such embodiment, the adhesive is sprayed through one or more openings of the nozzle. The openings can be configured to generate droplets of adhesive having a diameter of about 20 to 30 microns.

[0043] Crosslinking can occur after the adhesive has been dispersed into the substrate. In one embodiment, the adhesive can, for example, comprise an adhesive resin that crosslinks after the adhesive is applied to the substrate. Adhesion (water resistance / solvent resistance) can be promoted by self-crosslinking when the solvent in the adhesive formulation evaporates or by heat activation during the drying process.

[0044] The adhesive can comprise various conventional materials, including natural base materials, such as starch, dextrin or guar gum, etc., or synthetic resins, such as EVA, PVA, PVOH, SBR and polyglycolide, etc. In certain embodiments, solvent-based adhesives are used, wherein bonding occurs when the solvent evaporates. The surfactant can be mixed with the adhesive before or after the adhesive is dispersed into the substrate.

[0045] After the nanoparticles have been dispersed into the substrate, the substrate can be coated with a second adhesive.

[0046] The substrate, the nanoparticles, or both can be electrostatically charged using triboelectric charging methods, corona discharge, electrostatic fiber spinning, hydrocharging, charging rods, or other known methods. The nanoparticles can be isolated in a suitable fluid medium (e.g., air, helium, nitrogen, oxygen, carbon dioxide, and water vapor, etc.) before being dispersed on the substrate.

[0047] In another aspect, a method for producing a fibrous material includes providing a fibrous substrate having a first surface and a second surface opposite the first surface, wherein the fibers include a binder composition. Nanoparticles are dispersed through the first surface of the substrate such that the nanoparticles are bonded to the binder composition at least between the first surface and the second surface of the substrate.

[0048] In one such embodiment, the substrate comprises a biocomponent fiber, wherein one of the components comprises an outer sheath that at least partially surrounds the inner core. The sheath may comprise a material that bonds to the nanoparticles. For example, the sheath may comprise a material that becomes sticky and / or flows when heated and / or dried. During the heating / drying step (as discussed below), the sheath portion of the fiber is heated to its melting point until it becomes sticky and / or flows to bond the nanoparticles to the substrate. In a preferred embodiment, bonding and drying are performed simultaneously.

[0049] The core of the biocomponent fiber can be concentric or non-concentric with the sheath. The latter embodiment increases the overall bulk of the biocomponent fiber. Of course, other configurations are possible. For example, the core can include shapes other than circular, such as dog-bone, square, triangle, or diamond, etc. Optionally, the fiber can include multiple cores, or it can be divided into three, four, or more quadrants.

[0050] The recitation herein of desirable objectives met by various embodiments of the specification is not intended to imply or represent that any or all of these objectives are present as essential features (either individually or collectively) in the most general embodiment of the specification or in any of its more specific embodiments.

[0051] BRIEF DESCRIPTION OF THE DRAWINGS

[0052] Figure 1is a side view of a fiber material with nanoparticles dispersed throughout a portion of the material;

[0053] Figure 2 is a side view of a fiber material with nanoparticles dispersed throughout the material;

[0054] Figure 3 is a side view of a fiber material with nanoparticles dispersed in a gradient manner within the material;

[0055] Figure 4 A double layer of filter media is shown;

[0056] Figures 5A-5C Biocomponent fibers incorporated into a fibrous material are shown;

[0057] Figure 6 A pleated fiber filter media is shown;

[0058] Figure 7 A representative air filter is shown;

[0059] Figure 8 A gas filter having a first support membrane layer and a second support membrane layer and a filter medium is shown;

[0060] Fig. 9A and 9B An apertured membrane used as a support membrane layer is shown;

[0061] Figures 10A-10E Various embodiments of open-pore membranes in which nanoparticles are incorporated into the membrane are shown;

[0062] Fig.11 A gas filter is shown;

[0063] Fig.12 A system for producing a fibrous material within a substrate is schematically shown;

[0064] Fig.13 A system for converting nanofiber clusters into individual nanoparticles is schematically shown;

[0065] Figures 14A-14C The photos are large nanofiber clusters, small nanofiber clusters and single nanoparticles.

[0066] Fig.15 Shows Fig.13 The system's injectors;

[0067] Fig.16 Shows Fig.13 A reactor of the system;

[0068] Fig.17 Another embodiment of a system for converting nanofiber clusters into individual nanoparticles is shown;

[0069] Fig.18 A system for producing a double-layer fiber material is shown;

[0070] Fig.19 A fiber material showing the dispersion of nanoparticles through the depth of the material;

[0071] Fig. 20 A fiber material having nanoparticles dispersed deep through the material and a scrim layer covering the nanoparticles is shown;

[0072] Fig.21 A double-layer fiber material having nanoparticles dispersed on the inner surface of the double layer is shown;

[0073] Fig. 22 An alternative embodiment of a system for producing fibrous material in a fluid stream is shown;

[0074] Fig.23A is a photograph of the fiber material without the use of a binder;

[0075] Fig. 23B is a photograph of a fibrous material having a binder;

[0076] Fig.24A is a photograph of a fibrous material having nanoparticles dispersed throughout the material in bundles or clusters; and

[0077] Fig. 24B is a photograph of a fiber material with the nanoparticles substantially uniformly dispersed throughout the material. DETAILED DESCRIPTION

[0078] This specification and the accompanying drawings illustrate exemplary embodiments, and should not be considered as limiting, and the claims define the scope of this specification, including equivalents. Without departing from the scope of this specification and the claims, various mechanical, composition, structural and operational changes can be made, including equivalents. In some cases, well-known structures and technologies have not yet been shown or described in detail, so as not to make the description unclear. The same numbers in two or more figures represent the same or similar elements. In addition, as long as feasible, the elements and related aspects described in detail with reference to an embodiment can be included in other embodiments that are not specifically shown or described. For example, if an element is described in detail with reference to an embodiment, and it is not described with reference to a second embodiment, the element can still be claimed to be included in the second embodiment. In addition, the description herein is for illustrative purposes only and does not necessarily reflect the actual shape, size or size of the system or the components shown.

[0079] It should be noted that, as used in this specification and the appended claims, the singular forms "a," "an," and "the," as well as any word used in the singular, include plural referents unless clearly and unambiguously limited to one referent. As used herein, the term "include" and its grammatical variations are intended to be non-limiting, such that recitation of items in a list does not exclude other like items that can be substituted or added to the listed items.

[0080] Unless otherwise indicated, any quantitative values ​​are approximate, whether or not stated with the word "about" or "approximately." The materials, methods, and examples described herein are illustrative only and not intended to be limiting.

[0081] Provided are systems, devices and methods for producing fibrous materials and products containing fibrous materials. The fibrous material can include a substrate, such as a sheet, layer, film, apertured film, net, mesh or other medium. The substrate comprises fibers and includes nanoparticles incorporated into and retained in at least a portion of the substrate. As used herein, the term "nanoparticle" means any particle having a size less than 1 micron on at least one axis or dimension. For example, a fiber having a diameter or width less than 1 micron and a length greater than 1 micron is a nanoparticle used herein.

[0082] In certain embodiments, each individual nanoparticle can be a small particle, and its size range is about 1 to about 1000 nanometers, preferably about 1 to about 650 nanometers. In the number size distribution, the particle size of at least half of the particles can be measured as 100 nanometers or below. Most of nanoparticles are usually only composed of hundreds of atoms. As the size of nanoparticles approaches atomic scale, material properties change. This is due to the increase in surface area and volume ratio, causing the surface atoms of the material to dominate the material properties. Due to the very small size of nanoparticles, compared with bulk materials (such as powders, plates, sheets or larger fibers), the surface area of ​​nanoparticles is very large compared to volume. This feature makes nanoparticles have undesirable optical, physical and chemical properties, because they are small enough to limit their electronics and produce quantum effects.

[0083] In some embodiments, the nanoparticles comprise nanofibers having at least one dimension (i.e., diameter, width, height, etc., depending on the cross-sectional shape of the fiber) less than 1 micron. The nanofibers may have continuous lengths, or the nanofibers may have discrete lengths, such as 1 to 100,000 microns, preferably about 100 to 10,000 microns.

[0084] The nonwoven substrate discussed herein can comprise the structure of single fiber or line interwoven, interlocked or bonded together.Nonwoven fabric can comprise sheet or web structure bonded together by mechanical, thermal or chemical entanglement fiber or filament (and by perforated film).They can be substantially flat porous sheet, which is directly made of independent fiber or molten plastic or plastic film.The example of suitable nonwoven material includes but is not limited to the fiber, layer or web of meltblowing, spunbond or spunlace, thermal bonding, bonding combing, air-laid, wet-laid, co-molding, needle punching, stitching, hydraulic entanglement etc.

[0085] In certain embodiments, substrate can comprise knitting and / or woven material. Knitted material can comprise any knitting pattern suitable for desired application. Knitted material suitable for filter application comprises weft knitting, warp knitting, knitted mesh, compressed knitted mesh etc. Woven material suitable for filter application comprises textile filter media, for example monofilament fabric, multifilament fabric, nylon net, polyester net, polypropylene net etc. Woven textile can be used for for example mesh filter press filter cloth, woven filter pad and other die-cutting parts, centrifuge filter bag, liquid filter bag, dust collector filter bag, bed dryer filter bag, rotary drum filter, filter belt, leaf filter and roll medium etc.

[0086] In some embodiments, the fibrous material may include a structure comprising mixed or entangled chopped fibers and / or filaments. As used herein, chopped fibers refer to fibers of limited length. As used herein, filaments refer to fibers with substantially continuous length. In some embodiments, the substrate may include chopped coarse fibers, microfibers, and / or fine fibers. As used herein, "fine fibers" refer to fibers with a diameter less than 1 micron, "coarse fibers" refer to fibers with a diameter greater than 10 microns, and microfibers are synthetic fibers with a diameter less than 10 microns.

[0087] In certain embodiments, nanoparticles are "deeply" dispersed in substrates. As used herein, the term "deeply" means that nanoparticles are dispersed across the first surface of substrates so that at least some nanoparticles are disposed between first and second relative surfaces in the internal structure of substrates or media. In certain embodiments, nanoparticles are dispersed throughout substantially the entire medium from the first surface to the relative second surface. In other embodiments, nanoparticles are dispersed in a portion of the medium from the first surface to a position between the first surface and the second surface.

[0088] In some embodiments, the nanoparticles are three-dimensionally distributed in space relative to the supporting fibers, which can increase the fiber surface area and microvolume within the fiber material. The three-dimensional distribution can also prevent complete clogging of specific portions of the fiber material, which is particularly useful in filter media because it allows fluids (e.g., air and other gases) to pass through the filter, thereby reducing the overall pressure drop across the filter.

[0089] In other embodiments, the nanoparticles are arranged with a density gradient across the thickness of the substrate, so that the density of the nanoparticles arranged near a surface is higher than the relative surface, or compared with the middle portion of the substrate, the density of the nanoparticles arranged on the surface is higher. The density gradient shown can be substantially linear, it can be reduced in the form of a series of discrete steps, or the gradient can be random (that is, the reduction of density is usually not linear or step-wise). This density gradient provides many advantageous features (as described below) for certain applications (such as filters).

[0090] Nanoparticles can include any suitable material, such as glass, biosoluble glass, ceramic materials, acrylic, carbon, metals (e.g., alumina), polymers (e.g., nylon, polyethylene terephthalate, etc.), polyvinyl chloride (PVC), polyolefins, polyacetals, polyesters, cellulose ethers, polyalkylene sulfides, poly(arylene oxides), polysulfones, modified polysulfone polymers and polyvinyl alcohol, polyamides, polystyrene, polyacrylonitrile, polyvinylidene chloride, polymethyl methacrylate, polyvinylidene fluoride, and any combination thereof.

[0091] In some embodiments, the nanoparticles can be made into bicomponent cut-out cakes and islands. Then, the filaments are stretched to obtain submicron filaments. The continuous filament nanofibers are cut according to the desired length (preferably about 100 to about 10,000 microns).

[0092] In some embodiments, nanoparticles are absorbents and adsorbents. In some embodiments, nanoparticles are activated carbon fibers or activated carbon powder. In some embodiments, nanoparticles are catalytic particles or catalytic fibers. In some embodiments, nanoparticles can be obtained by feeding submicron fiber nonwovens to pulverizer or crusher or trimmer, wherein the bonded nonwoven enters, and obtains short-cut fibers. For example, low weight biocomponent melt-blown or nano melt-blown fabrics can be fed to pulverizer, and submicron nanoparticles can be obtained.

[0093] In some embodiments, different nanoparticles can be mixed. For example, nanofibers and nanobeads can be mixed. Two different nanofibers with different melting points can also be mixed so that the nanoparticles with a lower melting point can serve as a binder for the nanofibers with a higher melting point. Nanoparticles with different diameters and different lengths can also be mixed.

[0094] In some embodiments, the nanoparticles are selected from environmentally sustainable raw materials. The nanoparticles may include biosoluble glass nanofibers, biodegradable nanoparticles, compostable nanoparticles, or recyclable compositions.

[0095] Different types of nanoparticles can be combined. Some nanoparticles can be functional nanoparticles. For example, functional nanoparticles can include activated carbon and / or antibacterial materials deposited on and / or attached to the fibers in the fiber material. This can improve the gas absorption efficiency of the fiber and the effectiveness of killing bacteria. In addition, the fiber product of the microfiber nonwoven fabric deposited with glass and carbon nanoparticles will provide filtering and deodorizing functions as a filter medium.

[0096] In some embodiments, nanoparticles are bonded to fibers by mechanical entanglement. This mechanical bonding can be supplemented with adhesives or bonding agents, as discussed in more detail below. In certain embodiments, nanoparticles are not curled (that is, they do not include the obvious wavy, curved, curled, coiled sawtooth or similar shapes associated with the nanoparticles in a relaxed state). In other embodiments, nanoparticles can have a coiled body structure with discrete lengths. For example, when these coiled nanofibers with discrete lengths are attached to fibers, they tangle with each other, and are also firmly attached to fibers, attached to fibers and attached to fibers around fibers, thereby forming modified fibers. In other embodiments, the attachment of nanofibers to microfibers is achieved by attracting static charge and / or van der Waals forces between fibers and nanoparticles.

[0097] Also provided are filter media and filters, such as air filters, masks, gas turbine and compressor intake filters and panel filters, etc., which include nanoparticles dispersed deeply in the filter media. In some embodiments, the filter includes one or more support layers bonded to the filter media. The support layer and / or the filter media may include nanoparticles dispersed deeply in the layer. In some embodiments, a polymer layer, a membrane layer or a membrane is provided, which includes one or more holes for gas or liquid to flow therethrough, and the nanoparticles are deeply arranged in the polymer layer. In other embodiments, the fiber material includes a flexible surface layer for use in finger bandage pads or masks, etc.

[0098] Provided herein are systems, devices and methods for producing fibrous materials and products containing fibrous materials (e.g., gas filters). Also provided are systems and methods for isolating individual nanoparticles in a gaseous medium (e.g., air, helium, nitrogen, oxygen, carbon dioxide, etc.) (rather than a liquid) and capable of being dispersed into another product, film, layer or substrate by airflow, aerosol, evaporator, spray or other suitable delivery mechanism.

[0099] Although the following description is mainly directed to fiber materials and filter media, it should be understood that the devices and methods disclosed herein can be easily adapted to various other applications. For example, the fiber materials disclosed herein can be used in household cleaning products, roofing and flooring products, automotive interiors and headliners, reusable bags, wall coverings, filtration devices, insulation materials, etc. In addition, the single nanoparticles isolated and generated in the methods described herein can be used in various coatings, composite materials and / or additives, for example, polymers, food packaging, flame retardants, fuel cells, batteries, capacitors, nanoceramics, lamps, material manufacturing, production methods, reinforcements for composite materials, cements and other materials, medical diagnostic applications, medical treatment devices or therapies, tissue engineering (e.g., scaffolds for bone or tissue repair), drinking water, industrial process fluids, food and beverage products, drugs and biologics, tissue imaging, medical treatment delivery, environmental applications (e.g., biodegradable compounds), etc.

[0100] Figure 1 A fibrous material or substrate 10 including a plurality of fibers 12 and nanoparticles 14 is shown. The substrate 10 has a first surface 16 and a second surface 18 opposite the first surface 16, and defines a width or thickness between the first and second surfaces 16, 18. The nanoparticles 14 have been deposited into the substrate through the first surface 16. As shown, the nanoparticles 14 penetrate through the first surface 16 to the "depth" between the first and second surfaces 16, 18 of the substrate 10. In some embodiments, the nanoparticles 14 penetrate from the first surface to at least 25% of the width or thickness between the first and second surfaces 16, 18, or more preferably penetrate to at least about 50% of the thickness. In other embodiments, the nanoparticles 14 substantially penetrate the substrate 10 throughout from the first surface 16 to the second surface 18.

[0101] Nanoparticles 14 preferably include individual nanoparticles (e.g., nanoparticles) that have been broken, separated, and isolated from one another prior to being dispersed into substrate 10. Fig. 24B Thus, the nanoparticles 14 are not present in the fiber product in the form of a layer, and there are no obvious bundles or bundles of nanofibers (e.g. Fig.24A This allows the nanoparticles to be more dispersed throughout the substrate, which in some applications (e.g., gas filters) provides a more effective filtration capability to filter out pollutants. In addition, this allows the nanoparticles in the fibrous material to have a greater areal density (in grams per square meter (gsm)) or "addition amount" within the material. The term "addition amount" as used herein means the areal density (gsm) of a material, fiber, or particle in a thin layer, sheet, or film of a material.

[0102] In certain embodiments, the nanoparticles may comprise about 0.1 g / m 2 About 20 g / m 2, preferably at least about 2.0 g / m 2 The specific amount of addition or surface density may depend on the application. For example, the applicant has found that a higher surface density or addition will increase the efficiency of the fiber material in filtering pollutants. Therefore, the specific amount of nanoparticles added may depend on the desired efficiency of the filter medium.

[0103] Figure 2 A fibrous material or substrate 20 is shown that includes a plurality of fibers 12 and nanoparticles 14. As shown, the nanoparticles 14 penetrate throughout the entire width of the substrate 20 from the first surface 16 to the second surface 18. In certain embodiments, the nanoparticles 14 are substantially dispersed throughout the fibers 12 of the substrate, such as Figure 2 In some embodiments, the density of nanoparticles located at the first surface 16 differs from the density of nanoparticles dispersed in the central portion of the substrate 20 between the surfaces 16, 18 by less than 50%. In some embodiments, the difference is less than 25%, preferably less than 10%. In some embodiments, the amount or number of individual nanoparticles dispersed in the central portion of the substrate 20 is at least about 50%, preferably at least about 75%, and more preferably at least about 90% of the amount of individual nanoparticles dispersed at or near the first surface 16.

[0104] In other embodiments, the nanoparticles 14 are arranged in a density gradient from the first surface 16 to the second surface 18. For example, Figure 3 A substrate 30 is shown in which the nanoparticles 14 form a density gradient, wherein the density of the nanoparticles 14 disposed near the first surface 16 is higher than the density of the nanoparticles 14 disposed near the second surface 18. In certain embodiments, the difference between the density of the nanoparticles located at the first surface 16 and the density of the nanoparticles dispersed at the second surface 18 is greater than about 75%. In some embodiments, the difference is greater than 50%. In some embodiments, the difference is greater than 25%. In certain embodiments, the amount or number of individual nanoparticles dispersed at or near the second surface 18 is less than about 50%, preferably less than about 25%, and more preferably less than about 10% of the amount of individual nanoparticles dispersed at or near the first surface 16.

[0105] Figure 3 The density gradient shown in FIG. 1 may be substantially linear from the first surface 16 to the second surface 18. Alternatively, the density of the nanoparticles 14 may decrease from the first surface 16 to the second surface 18 in a series of discrete steps, or the gradient may be random (i.e., the decrease in density is generally not linear or step-like).

[0106] In other embodiments, nanoparticles can be added to the substrate from the first and second surfaces 16, 18. In these embodiments, the surface density or "addition amount" at the first and second surfaces 16, 18 can be substantially equal to each other, or they can be different depending on the application. In these embodiments, the surface density or "addition amount" present in the middle of the substrate is lower than the surface density or "addition amount" at the surfaces 16, 18. For example, the surface density in the middle of the substrate can be about 75% of the surface density at the surfaces 16, 18, or can be about 50%, 40%, or 25%.

[0107] The distribution of nanoparticles across the thickness of the surface material can be measured, for example, using imaging techniques. An enlarged view of the fiber product is taken using an electron microscope or other technique at a horizontal cross section of the product at the middle of the product thickness, which can be compared to an image taken at the upper or lower surface of the product, or all three images can be compared to determine the extent of variation in the amount of deposited nanoparticles. Computer image analysis processing can be employed. For example, in Figure 3 In the present invention, a cross section can be taken at line AA, and a cross section can be taken at line BB. A top view of each cross section can be obtained by an electron microscope, a scanning electron microscope, and other microscopes. For example, a top view of a cross section obtained at section AA can be compared with a top view obtained at section BB. The number of microfibers, the number of nanoparticles, or both in samples of the same two-dimensional size can be evaluated and compared. In addition, imaging techniques can be used on three-dimensional samples. These techniques can be used to evaluate the orientation and other characteristics of the fibers. These techniques can be used to determine that the nanoparticles have been deposited deep into the substrate, have been substantially deposited in a large part of the substrate, substantially in the entire depth of the substrate, or deep in a portion of the substrate.

[0108] The fibers of the contemplated substrate may be produced by any process including, but not limited to, air laying, spinneret, gel spinning, melt spinning, wet spinning, dry spinning, islands in the sea staple fibers or spunbond, segmented cake staple fibers or spunbond, etc. Such processes have been described in U.S. Pat. Nos. 4,406,950, 6,338,814, 6,616,435, 6,861,142, 7,252,493, 7,300,272, 7,309,430, 7,422,071, 7,431,869, 7,504,348, 7,774,077 9,522,357, 9,993,761 and U.S. Patent Publication Nos. 2009 / 266,759, the entire disclosures of which are hereby incorporated by reference herein for all purposes.

[0109] The cross-section of the contemplated fibers may have a variety of shapes, including but not limited to round, kidney bean, dog bone, trilobal, barbell, bow tie, star, and Y-shaped, etc. These shapes and / or other conventional shapes may be used with the embodiments to obtain the desired performance characteristics. The fibers in the substrate are held connected to each other by thermal bonding, chemical bonding, interentanglement, use of a binder (e.g., adhesive), etc.

[0110] The fibers may be man-made or natural. Suitable materials for the fibers include, but are not limited to, polypropylene, polyester (PET), PEN polyester, PCT polyester, polypropylene, PBT polyester, copolyamide, polyethylene, high density polyethylene ("HDPE"), LLDPE, cross-linked polyethylene, polycarbonate, polyacrylate, polyacrylonitrile, polyfumaronitrile, polystyrene, styrene maleic anhydride, polymethylpentene, cyclic olefin copolymers or fluorinated polymers, polytetrafluoroethylene, perfluoroethylene and hexafluoropropylene or copolymers (such as P(VDF-TrFE)) or terpolymers (such as P(VDF-T rFE-CFE)), propylene, polyimide, polyetherketone, cellulose ester, nylon and polyamide, polymethacrylic acid, poly(methyl methacrylate), polyoxymethylene, polysulfonate, acrylic acid, styrenated acrylic acid, pre-oxidized acrylic acid, fluorinated acrylic acid, vinyl acetate, vinyl acrylic acid, ethylene vinyl acetate, styrene-butadiene, ethylene / vinyl chloride, vinyl acetate copolymer, latex, polyester copolymer, carboxylated styrene acrylic or vinyl acetate, epoxy resin, acrylic multipolymer, phenolic resin, polyurethane, cellulose, styrene or any combination thereof. Other conventional fiber materials are contemplated.

[0111] The fibers can include fibers of different sizes, typically having diameters of about 1 to 1000 microns and lengths of about half an inch to three inches. The fibers can be configured as a gradient density media, where the pore size decreases from the upper surface (upstream) to the lower surface (downstream) of the filter to increase capture efficiency and dust holding capacity. This configuration also allows different quantities of nanoparticles to be dispersed into the filter media at different depths. For example, the upstream side of the filter media can have the largest fiber size to allow for more void space and a greater density of nanoparticles, while the downstream side of the filter media has smaller sized fibers to provide a lower density of nanoparticles. Alternatively, the structure can be reversed to provide a higher density of nanoparticles in the downstream portion of the filter media.

[0112] The fibers in the media may be held connected to other fibers by thermal bonding, chemical bonding, or entanglement. Bicomponent fibers may be used, particularly in mechanical filtration, and are formed by extruding two polymers from the same spinneret, both polymers being contained in the same filament. Suitable materials for bicomponent fibers include, but are not limited to, polypropylene (PP) / polyethylene (PE), polyethylene terephthalate (PET) / polypropylene (PP), and the like.

[0113] In some embodiments, the substrate may comprise a "high loft" nonwoven material comprising spunbond or through-air bonded carded nonwoven fibers. As used herein, the term "high loft" means that the volume of the void space is greater than the volume of the total solids. In through-air bonded carded nonwoven fibers, the loft of the substrate can be controlled in various ways known to those skilled in the art. For example, the loft can be increased by applying less compressive force to the medium during the bonding process. In another example, a high loft nonwoven material can be produced with fibers having a greater thickness (e.g., a thickness greater than 3 denier, such as 5 denier or greater, 6 denier or greater) (discussed in more detail below). In other embodiments, loft can be increased by using non-concentric biocomponent fibers, such as Figure 5C shown and discussed in more detail below.

[0114] In certain embodiments, the fiber may include a silicon-based coating to improve the efficiency of the filter media in capturing pollutants, particularly pollutants within the E2 and E3 particle groups. The silicon-based coating may include a reactive silicon coarse emulsion. Silicon emulsions may include, for example, dimethyl silicon emulsions, amino-type silicon emulsions, organofunctional silicon emulsions, resin-type silicon emulsions, film-forming silicon emulsions, and the like. In one embodiment, the reactive silicon coarse emulsion comprises amino-functional polydimethylsiloxane and / or polyethylene glycol monotridecyl ether. Suitable silicon coatings are described in commonly assigned U.S. Provisional Patent Application Serial No. 63 / 406,686, filed on September 14, 2022, the full disclosure of which is incorporated herein by reference.

[0115] The filter media may contain a charge additive to modify the triboelectric charge of the fibers and increase the stability and / or duration of the triboelectric charge in the filter. This improves the overall filtration efficiency of the filter without compromising other important properties of the filter, such as life, dust holding capacity, and pressure drop or air flow through the filter. Charge additives suitable for triboelectric charging are described in commonly assigned provisional patent application serial number 63 / 410,731 filed on September 28, 2022, the entire disclosure of which is hereby incorporated by reference herein for all purposes.

[0116] Fiber can have the thickness suitable for application.In some embodiments, at least one dimension of fiber is about 1 to about 10,000 micron or about 1 to about 1,000 micron or about 10 to 100 micron.The thickness of fiber can also be measured with denier, and denier is the measurement unit of fiber linear mass density.In some embodiments, the linear density of fiber can be about 1 denier to about 10 denier.Nanoparticle is at least one dimension is about 1 to about 1,000 nanometer or about 1 to about 100 nanometer fiber.The size of above-mentioned fiber and nanoparticle can be diameter or width, depends on the shape of fiber or nanoparticle.

[0117] For gas filters, such as pleated or non-pleated air filters, the linear density of the fibers can be from about 1 denier to about 10 denier. The filter media can contain fibers having the same or different linear densities.

[0118] The linear density of the fibers in air filters is typically about 3 deniers or less to ensure that the fibers are small enough to capture pollutants passing through the filter. Applicants have unexpectedly discovered that by using nanoparticles dispersed in the filter media, the fibers can have a greater linear density, for example, greater than 3 deniers. This is because the nanoparticles provide significant filtering capabilities. In some cases, the linear density of the fibers can be greater than 3 deniers, 5 deniers or greater, 6 deniers or greater, or as large as 7-10 deniers.

[0119] Applicants have also discovered that in some applications, fibers having a linear density greater than that used in conventional filters (e.g., greater than about 3 denier) provide more open space or pores within the filter media, which allows a greater density of nanoparticles to be dispersed therein. While this may be counter-intuitive to one skilled in the art, Applicants have discovered that incorporating nanoparticles into fibers having a greater linear density actually improves the overall efficiency of the filter.

[0120] In some embodiments, the filter media can include at least two different fiber thicknesses or linear densities to provide at least two different filter layers within the same filter media. For example, in some cases, a portion of the filter media will include fibers with a linear density greater than 3 deniers, for example, 5 deniers or greater or 6 deniers or greater. Another portion of the filter media will contain fibers with a more standard linear density of 3 deniers or less. This double-layer filter media creates a first filter portion and a second filter portion, the first filter portion mainly using nanoparticles with a high density in the fibers of the larger thickness to filter pollutants; the second filter portion mainly uses fibers with a lower linear density to filter pollutants, but both portions can include nanoparticles dispersed throughout the fibers. In some embodiments, the filter media can include three or more separate portions or layers, each with a different range of denier fibers.

[0121] Figure 4 A dual-layer filter media is shown, which includes a first substrate 40 having a first surface 42 and a second surface 44 opposite the first surface; and a second substrate 50 having a first surface 52 and a second surface 54 opposite the first surface. The second surface 44 of the substrate 40 is bonded to the second surface 54 of the first substrate in any manner known to those skilled in the art. The first substrate 40 contains fibers 46 with a relatively small linear density, for example, about 3 denier or less. The second substrate 50 contains fibers 56 with a relatively large linear density, for example, about 3 denier or greater, such as 5 denier, 6 denier or greater. The second substrate 50 also includes individual nanoparticles 58 dispersed throughout the fibers 56 and bonded to the fibers 56 and / or retained by the second substrate 50. The first substrate 40 may also include nanoparticles, or may not include nanoparticles.

[0122] The first substrate 40 is configured to filter pollutants primarily using fibers 46, but as previously described, the first substrate 40 may also include nanoparticles. The second substrate 50 is configured to filter pollutants using fibers 56 and nanoparticles 58.

[0123] In some embodiments, the substrate may contain additives, such as antimicrobial and / or antiviral compositions, such as silver, zinc, copper, silicone, tributyltin, organic compounds containing chlorine, bromine or fluorine compounds.

[0124] The fibers may include biocomponent fibers including two or more different fibers bonded to each other. The fibers may include the same material or different materials.

[0125] Figures 5A-5C Various examples of biocomponent fibers that can be used with the fiber materials disclosed herein are shown. Figure 5A A fiber 60 is shown having a core fiber 62 and a surrounding sheath fiber 64. In this embodiment, the core 62 is substantially concentric with the sheath. Figure 5B A biocomponent fiber 70 is shown having first and second fibers 72, 74 arranged side-by-side with one another. Figure 5C A biocomponent fiber 80 is shown having a core fiber 82 and a sheath fiber 84. In this embodiment, the core 82 is non-concentric with respect to the longitudinal axis of the sheath 84, which increases the overall loft of the biocomponent fiber. Of course, other configurations are possible. For example, the core can include shapes other than circular, such as dog-bone, square, triangle, diamond, etc. Alternatively, the fiber can include multiple cores, or it can be divided into three, four, or more quadrants.

[0126] In certain embodiments, the fibrous material (i.e., fiber and / or nanoparticle) can be electrostatically charged so that, for example, pollutants can be captured by mechanical and electrostatic filtration. The bonding between the fiber and the nanoparticle can also be enhanced by electrostatically charging the nanoparticle, the fiber, or both. For example, in certain embodiments, the fiber is electrostatically charged so that mechanical filtration can be achieved by nanoparticles, and electrostatic filtration can be achieved by an electret substrate. Electrostatic or electret substrates can be high-loft triboelectric filtration media made by combing and acupuncture. In one of these embodiments, preferably nanoparticles are deposited in the substrate before acupuncture, and then electrostatic fibers and nanoparticles are acupunctured together.

[0127] The substrate, nanoparticles, or both may be electrostatically charged using triboelectric charging methods, corona discharge, electrostatic fiber spinning, hydrocharging, charging rods, or other known methods. Corona charging is suitable for charging single polymer fibers or fiber blends or fabrics. Triboelectric charging can be suitable for charging fibers with different electronegativity. Electrostatic fiber spinning combines the charging of polymers and the spinning of fibers into a one-step process. Charging additives suitable for triboelectric charging are described in commonly assigned provisional patent application serial number 63 / 410,731 filed on September 28, 2022, the entire disclosure of which is hereby incorporated by reference herein for all purposes.

[0128] Nanoparticles can be selected to have different triboelectric properties relative to the fibers to enhance particle removal using the triboelectric effect. With this approach, the resulting nanoparticles are formed in an electric field and are less susceptible to contamination by chemicals that can mitigate the triboelectric effect. Nanoparticles can also be used with different adsorption properties or surface charge characteristics than the macrofibers, such as for oil or water filtration. This difference can be used to enhance or create local electric field gradients within the filter media to enhance particle removal. The nanoparticles and macrofibers can have different wetting characteristics.

[0129] The fiber material may include a binder or bonding material, such as an adhesive or binder, to promote bonding between fibers and / or retention of nanoparticles in the matrix, so that the nanoparticles can adhere to the fibers or otherwise be retained by the fibers within the matrix to form a stable matrix. The binder or bonding material is preferably present in a relatively small amount to bond a single nanoparticle to the fibers throughout the matrix.

[0130] The adhesive may comprise a variety of conventional materials, including natural based materials such as starch, dextrin, guar gum, etc., or synthetic resins such as EVA, PVA, PVOH, SBR, polyglycolide, etc. In certain embodiments, a solvent based adhesive is used, wherein bonding occurs upon evaporation of the solvent.

[0131] In a preferred embodiment, the adhesive or adhesive material comprises dextrin. In yet another embodiment, the adhesive comprises a composition of various substances (e.g., water, 2-hexyloxyethanol, isopropanolamine, sodium dodecylbenzene sulfonate, lauramine oxide, and ammonium hydroxide). In yet another embodiment, the adhesive comprises at least PVOH. The adhesive can be a solution, emulsion, suspension, hot melt, curable, pure, and / or a combination.

[0132] In some embodiments, adhesive resin is used, and adhesive resin can be cross-linked after adhesive is applied to substrate. Adhesion (water resistance / solvent resistance) can be promoted by self-crosslinking when solvent evaporates in adhesive formulation or heat activation in drying process. For some adhesives, crosslinking can be achieved by electromagnetic radiation (including but not limited to RF, UV or electron beam) of high energy wavelength. The amount of adhesive can be controlled by adjusting the nozzle size of sprayer 140 or the flow rate of control adhesive composition. Adhesive can be applied using nozzle, dip coating or other methods.

[0133] In some embodiments, the adhesive or adhesive material may include a surfactant to reduce the surface or interfacial tension of the adhesive, thereby increasing its dispersibility and wettability, and making it easier for the adhesive to penetrate into a substrate at a certain depth. Suitable surfactants for use with the adhesive disclosed herein include nonionic surfactants, anionic surfactants, cationic surfactants, and amphoteric surfactants, such as sodium stearate, 4-(5-dodecyl)benzenesulfonate, sodium dodecylbenzenesulfonate wetting agents, docusate (dioctyl sodium sulfosuccinate), alkyl ether phosphates, benzalkonium chloride (BAC), and perfluorooctane sulfonate (PFOS), etc.

[0134] In some embodiments, the substrate includes its own adhesive composition. In these embodiments, the adhesive or adhesive material may or may not be added to the substrate. In one such embodiment, the substrate comprises biocomponent fibers, wherein one of the components comprises an outer sheath at least partially surrounding an inner core (see Figure 5A and 5C ).

[0135] The sheath may comprise a material that bonds to the nanoparticles. For example, the sheath may comprise a material that becomes sticky and / or flows when heated and / or dried. During the heating / drying step (as discussed below), the sheath portion of the fiber is heated to its melting point until it becomes sticky and / or flows to bond the nanoparticles to the substrate. In a preferred embodiment, bonding and drying are performed simultaneously.

[0136] Fig.23A is a magnified image of a fiber product having nanoparticles deposited therein without the use of a binder material. Fig. 23Bis an enlarged image of a fiber product in which a binder material of dextrin and water is used to adhere the nanoparticles to the fibers. As shown, with the use of a binder, the nanoparticles are more uniformly adhered to the fibers.

[0137] exist Fig.23A and 23B In the example of , a substrate having bicomponent microfibers is used, the inner portion of the bicomponent microfibers being polyester and the outer portion being high density polyethylene ("HDPE"). Fig.23A A microfiber fiber product having a bicomponent microfiber substrate is shown, in which a layer of biosoluble glass nanofibers is deposited only on the surface of the substrate, relying on electrostatic forces to retain the nanofibers. Fig.23A Agglomeration of nanofibers can be seen in the substrate, and the retention of nanofibers is poor. The substrate can be produced using meltblowing, spunbonding, or other methods described herein.

[0138] exist Fig. 23B In the example, an adhesive material is used. The substrate is sprayed with a mixture of dextrin and water, and nanoparticles are applied to the substrate, where the uniformity of the nanofibers is higher and the retention rate is greater. In other examples, any adhesive material disclosed herein can be used. In addition, nanoparticles of biosoluble glass have been deposited deep into the substrate. In this example, the two-component microfiber substrate itself has a MERV rating of 4 to 10, which can be achieved using any method described herein. In one example, due to the deposition of nanoparticles deep into the substrate and with static charge, a microfiber substrate with an initial MERV of 8 has been used to produce a fiber product with a MERV of 13. In another example, a microfiber substrate with an initial MERV of 6 has been used to produce a fiber product with a MERV of 15. The substrate is provided on a roll, and in a roll-to-roll continuous process, the fiber product can be produced on a commercial scale, such as any process and method described herein. In the example, the roll-to-roll process runs at a speed of 30 feet per minute.

[0139] In certain embodiments, the fibrous materials discussed herein can be used as part of a filtration device that captures or absorbs contaminants, such as liquid filters, gas filters for home and commercial air filtration, surgical masks or other face masks, etc. The filtration device can be a mechanical filter, an absorption filter, a barrier filter, an ion exchange filter, a reverse penetration filter, a surface filter, a depth filter, etc., and can be designed to remove many different types of contaminants from air, water, or other substances.

[0140] In one such embodiment, the fibrous material is incorporated into an air filter that removes particles and pollutants from the air, such as a HEPA filter (i.e., a pleated mechanical air filter), a UV filter, an electrostatic filter, a washable filter, a media filter, a glass fiber filter, a pleated or non-pleated air filter, an activated carbon filter, a bag filter, a V-Bank compact filter, a filter sheet, a flat cell filter, and a filter cartridge, etc. The fibrous material can comprise the filter medium of the air filter, and can be supported by a support layer, a scrim layer, or can be included in other layers or materials. Applicants have found that, as discussed herein, incorporating nanoparticles into the fibrous material significantly improves the efficiency of the air filter without compromising other factors, such as the pressure drop (i.e., air flow) through the filter. In addition, these materials increase the overall dust holding capacity, thereby extending the life of the filter, particularly compared to filters that only or primarily rely on electrostatic effects to improve efficiency.

[0141] Traditional home and commercial air filters, such as HEPA filters, are typically rated based on the filter's ability to capture particles ranging from approximately 0.3 to 10 microns. This rating is called the Minimum Efficiency Reporting Value, or MERV, and is established by the American Society of Heating, Refrigerating and Air-Conditioning Engineers (ASHRAE). MERV ratings range from 1-16, with higher values ​​indicating greater efficiency in capturing a particular type of particle. Traditional mechanical air filters typically report a MERV rating of about 8 for the fiber filter material.

[0142] Air filters are usually rated based on their initial efficiency (i.e., the efficiency of the air filter before use) and their efficiency over time and use. The latter efficiency is usually tested through a conditioning procedure, known as Annex J of ASHRAE Standard 52.2.

[0143] The air filters provided herein have an initial MERV rating greater than about 10 and a pressure drop of less than about 0.5 inches of water column. In some cases, the initial MERV rating is about 11 and the pressure drop is equal to or less than about 0.17 inches of water column, or the initial MERV rating is about 13 and the pressure drop is equal to or less than about 0.36 inches of water column, or the initial MERV rating is about 14 and the pressure drop is equal to or less than about 0.5 inches of water column.

[0144] The gas filters provided herein have a MERV rating of 10 or higher after conditioning according to ASHRAE Standard 52.2, Appendix J. In some embodiments, the MERV rating is 13 or higher after conditioning according to ASHRAE Standard 52.2, ISO Standard 16890, or any other acceptable standard in the industry.

[0145] The MERV ratings of the fiber filter media discussed herein will vary based on many factors, including the type and size of fibers used in the filter media, the density of individual nanoparticles within the filter media, the width of the filter media, the number and size of pleats (if any), etc. MERV ratings can be measured for sheets of fiber products as well as fiber products formed into pleated filter media, and the pressure drop for each product can be different. Likewise, the pressure drop across the filter media will also depend on many factors, including those described above.

[0146] One factor that affects the MERV rating and pressure drop is the density or amount of the nanoparticles in the substrate relative to the density of the fibers in the substrate. Applicants have found that the lower the ratio between the substrate density and the nanoparticle density, the higher the MERV rating of the filter and the higher the pressure drop. In certain embodiments, the nanoparticle surface density of the filter media described herein is about 0.1 g / m 2 About 20 g / m 2 , preferably at least about 2 g / m 2 .

[0147] In some cases, the density of the nanoparticles will also depend on the density of the actual filter media (i.e., the density of the coarse fibers). As discussed in more detail below with reference to Table 2 below, a density ratio of about 67 (substrate gsm divided by added nanoparticle gsm) results in a pressure drop of about 0.14 inches of water column and an initial MERV rating of 10. A density ratio of about 33.4 increases the MERV rating to 10, but only results in a pressure drop of about 0.17. A density ratio of about 22.3 increases the initial MERV rating to about 12 with a pressure drop of about 0.24 inches of water column.

[0148] Thus, the efficiency or MERV rating of the filter can be increased as the amount of nanoparticles added increases. In particular, the applicant has found that, for example, an addition amount of at least 2 g / m 2 A filter with a MERV rating of approximately 10 can be achieved. 4 or 6 g / m 2 The addition of 10 g / m 2 Addition levels of 1% or more produce filters with a MERV rating of 15 or higher.

[0149] Applicants have also discovered that including fibers with greater thickness or linear density results in larger pore sizes, and therefore greater pore volumes, thereby achieving a higher density of nanoparticles within the substrate. This results in higher MERV ratings and pressure drops (as discussed below with reference to Table 2). For example, Applicants have been able to produce air filters with a MERV rating of 14 and a pressure drop of 0.5 inches of water column using 5 denier biocomponent fibers. Similarly, Applicants were able to produce filters with a MERV rating of 13 and a pressure drop of only about 0.29 inches of water column using 5 denier biocomponent fibers.

[0150] Figure 6 An example of a pleated filter media 90 is shown in FIG. Depending on the application, the filter 90 may include about 0 to 10 pleats per inch. The filter media may be mounted in a cardboard or metal frame and used as an easily replaceable filter product ( Figure 7 ). As shown, a gas filter 94 is produced using the fibrous materials described herein. As shown, the filter 94 includes a pleated fiber filter medium 96 and a support layer 98 that provides rigidity and structure to the filter medium 96.

[0151] Fig.11 A gas filter 109 produced using the fibrous material described herein is shown. The gas filter 109 includes a fibrous substrate having fibers and nanoparticles dispersed deep within the substrate. The substrate is then rolled into a cylinder, cone, or other suitable shape and can be used in applications such as gas turbine and compressor intake filters, panel filters, and the like.

[0152] Other types of filters that can be developed using the fiber materials disclosed herein include conical filter cartridges, square end cap filter cartridges, bag filters, V-Bank compact filters, plate filters, flat cell filters, pleated or non-pleated bag filter cartridges, and the like.

[0153] The fiber products disclosed herein can be used in medical masks or other medical applications, such as filter cartridges in respirators. Medical masks are intended to protect medical staff and / or patients from microorganisms and other substances. For example, medical masks can block bacteria (e.g., which can be about 3 microns in size) and viruses (e.g., which can be about 0.1 microns in size). The mask is made of multiple layers of fiber material and has ear loops, laces or other structures for attaching the mask to the face of a person. Metal wire can be incorporated into at least the upper part of the mask so that at least this part fits the face of a person. The mask can include a rigid polymer structure for fixing the multiple layers of fiber material in front of the face of a person. In one example, the mask has three layers. The outer layer and the inner layer contain a fiber material (e.g., spunbond polypropylene) that provides air permeability, but any material mentioned herein can also be used. The middle layer is located between the inner layer and the outer layer and contains a microfiber substrate having nanoparticles deposited into the substrate at a certain depth to provide an initial MERV greater than 8, preferably a MERV greater than 10, and more preferably a MERV of 13 or greater. The pressure drop through the mask is 3 to 6 mm H2O, more preferably 4 mm H2O for breathability. The mask is expected to have an efficiency of about 95%. Other examples of masks have four or more layers. Multiple layers of fiber products can be combined into a single mask.

[0154] In certain embodiments, the fibrous material may be included in a film or layer that includes holes, pores, or perforations. The holes may be embossed into a pattern (e.g., circles, diamonds, hexagons, rectangles, triangles, rectangles, etc.) and then stretched until holes are formed in the thinned areas produced by the embossing. Such an open-cell substrate may be formed from a variety of polymers (e.g., polypropylene, polyethylene, high-density polyethylene ("HDPE"), etc.). The polymer layer may, for example, comprise an extruded film. Open-cell films are commercially available and are available as The substrate is provided in the form of a roll and the nanofibers are deposited into the substrate in a roll-to-roll process. Figures 10A-10E Examples of apertured films formed using the methods described herein are shown.

[0155] In other embodiments, the gas filter comprises a filter medium and a substantially rigid support layer bonded to the filter medium. The support layer includes fibers and individual nanoparticles dispersed deep within the layer. The nanoparticles are configured to filter contaminants that pass through the support layer.

[0156] refer to Figure 8 , the composite filter member 814 includes an internal filter substrate 812 and one or more filter support members or membrane layers 810. The support member 810 can be formed by an extruded sheet of a polymer, such as a polypropylene film, a high-density polyethylene film, a polylactic acid film, or a thermoplastic polymer material, such as an extrudable fluoroplastic material, in an embodiment, a perfluoroalkoxyalkane (PFA) copolymer made from comonomers polytetrafluoroethylene and perfluoroalkyl vinyl ether. However, other polymer materials can be used, such as fluoroplastics, such as ethylene trifluorochloroethylene (ECTFE), ethylene tetrafluoroethylene (ETFE), or polyvinylidene fluoride (PVDF).

[0157] In certain embodiments, the support membrane layer 810 comprises individual nanoparticles dispersed deep within the membrane layer 810, as described above. The nanoparticles allow the support membrane layer to filter at least some contaminants that pass through the filter membrane layer 814, i.e., in addition to the filtration provided by the internal filter substrate 812. In other embodiments, the filter substrate 812 and / or the support membrane layer 810 include such nanoparticles.

[0158] Fluoroplastic materials such as PFA are well suited for use in filters for cleaning semiconductor components and other environments where extremely high cleanliness is required and the potential for contamination is minimized. Such support membrane layers are designed to direct fluids along their surfaces and also to direct fluids through the structure to the underlying filter substrate to remove unwanted particles from the filtrate.

[0159] like Fig. 9A and 9BAs shown, the support film layer 810 may include a plurality of holes 828. The shape of the holes is preferably circular, but it will be appreciated that other shapes are also possible, such as square, rectangular, triangular, etc. The substrate may be wound into a roll, then unwound and directed through a punching machine to form the desired predetermined pattern of holes 828 in the Z direction ( Fig. 9A ). Optionally, after being set up, the sheet can be directed through a punch press in a continuous operation to form a predetermined pattern of holes 828 therein.

[0160] refer to Fig. 9B After opening the pores, the filter support member can be stretched in the machine direction, as shown by double-headed arrow 940, to elongate the pores 828 to provide a larger open area for the passage of the fluid to be filtered by the filter media or substrate 812.

[0161] In an alternative embodiment, the support membrane layer 810 can be porous (i.e., not having pores 828, or in addition to having pores 828). In this embodiment, additional fluid flow can be achieved through a substantially porous support membrane layer. In an exemplary embodiment, the porosity value of the support membrane layer is at least 0.5 or 50%, preferably at least 0.8 or 80%, and more preferably about 0.86 or 86%. The porosity value is defined as the non-solid or pore volume fraction of the total volume of the material. A more complete description of this composite filter medium can be found in PCT Application Serial No. US2020 / 040941, the complete disclosure of which is incorporated herein by reference in its entirety for all purposes.

[0162] The support membrane layer of the present filter can be prepared by any method known to those skilled in the art. Fig. 9A and 9B In one example shown, the support film layer includes ribs. For example, the support film layer can be made by extruding a polymer material to form a sheet and then passing the sheet through a nip area provided by opposing rollers; at least one roller has an outer surface with countersunk grooves. The countersunk grooves in one roller are aligned with the outer surface or the countersunk grooves of the other roller in the nip area to form a ribbed sheet having ribs upstanding from at least one surface of the sheet. Optionally, the ribs can be formed in an extrusion process or a known embossing method. Once the ribs are formed, the support film layer can be wound into a roll, subsequently unwound and directed through a press to form a desired predetermined pattern of holes in the Z direction thereof. Optionally, after setting, the support film layer can be continuously operated to guide the support film layer through a punch press to form a predetermined pattern of holes therein, such as Fig. 9A Optionally, the support film layer can be stretched in the machine direction ( Fig. 9B The pores are elongated to provide a larger open area for the passage of a fluid to be filtered through, for example, a filter layer or a substrate.

[0163] Fig.12 The overall system 110 for producing the above-mentioned fiber materials and other products is schematically depicted. As shown, the system 110 includes a feeder 120 for advancing a substrate 130 of fibrous fibers or other materials during the production process. The system 100 also includes a coater 140, a fiberizing system 150, and a heating and / or drying device 160. In certain embodiments, the system 100 also includes a vacuum or other negative pressure source 170 located below the substrate 130, which is opposite to the fiberizing system 150.

[0164] In one embodiment, the feeder 120 includes a winder 122 at the downstream end of the process and an unwinder 124 at the upstream end, which continuously winds the substrate 130 through the system 100. In certain embodiments, the feeder 120 may also include a support surface (not shown) extending between the winders for supporting the substrate 130 as it moves downstream through the system 100. In other embodiments, the substrate is unwound directly from the unwinder 124 to the winder 122 without another support surface.

[0165] The coater 140 is configured to spray droplets of an adhesive or bonding material (e.g., an adhesive or a binder) onto the substrate 130 so that the nanoparticles can adhere to the fibers within the substrate 130 to form a stable matrix. The adhesive is preferably present in a relatively small amount to bond a single nanoparticle to the fibers throughout the substrate 130. In a preferred embodiment, the coater 140 includes a nozzle sized to generate adhesive droplets having a diameter of about 20 to 30 microns to increase the penetration depth of the adhesive through the substrate 130. Of course, the droplet size may be affected by many other parameters, including air pressure, air volume, air temperature, humidity, spray horn design, rheology / viscosity of the adhesive, and carrier, etc.

[0166] Of course, it should be recognized that coating the substrate with the adhesive or bonding material can be achieved using other coating methods including ultrasonic spraying, dip coating, spin coating, gravure coating, kiss roll coating, screen coating, powder coating, electrostatic, sputtering or similar coating techniques.

[0167] As described above, the adhesive may include various conventional materials, including natural based materials such as starch, dextrin, guar gum, etc., or synthetic resins such as EVA, PVA, PVOH, SBR, etc. In certain embodiments, a solvent based adhesive is used, wherein bonding occurs when the solvent evaporates.

[0168] In a preferred embodiment, the adhesive comprises dextrin. In another embodiment, the adhesive comprises a composition of various substances (e.g., water, 2-hexyloxyethanol, isopropanolamine, sodium dodecylbenzene sulfonate, lauramine oxide, and ammonium hydroxide). In another embodiment, the adhesive comprises PVOH. The adhesive can be a solution, emulsion, suspension, hot melt, curable, pure, and / or a combination.

[0169] In some embodiments, an adhesive resin is used, and the adhesive resin can be cross-linked after the adhesive is applied to the substrate 130. Adhesion (water resistance / solvent resistance) can be promoted by self-crosslinking when the solvent in the adhesive formulation evaporates or thermal activation during drying. For some adhesives, crosslinking can be achieved by electromagnetic radiation of high energy wavelengths (including but not limited to RF, UV or electron beams). The amount of the adhesive can be controlled by adjusting the nozzle size of the sprayer 140 or controlling the flow rate of the adhesive composition.

[0170] In some embodiments, the adhesive may include a surfactant to reduce the surface or interfacial tension of the adhesive, thereby increasing its dispersibility and wettability and making it easier for the adhesive to penetrate deep into the substrate. Suitable surfactants for use with the adhesive disclosed herein include nonionic, anionic, cationic and amphoteric surfactants, such as sodium stearate, 4-(5-dodecyl)benzenesulfonate, sodium dodecylbenzenesulfonate wetting agents, docusate (dioctyl sodium sulfosuccinate), alkyl ether phosphates, benzalkonium chloride (BAC) and perfluorooctane sulfonate (PFOS) and the like.

[0171] In some embodiments, sprayer 140 is located upstream of fiberizing system 150 to spray the binder before depositing the nanoparticles. In other embodiments, sprayer 140 is located downstream of fiberizing system 150 to spray the binder after depositing the nanoparticles. In other embodiments, system 100 includes two spray layers; one located upstream of fiberizing system 150, and a second sprayer (not shown) located downstream of fiberizing system 150 to coat substrate 130 with a second binder after depositing the nanoparticles.

[0172] In some embodiments, each sprayer 140 has more than one nozzle head. For example, the nozzle heads can be arranged in series to obtain better uniformity or increase the fiber spray width. Alternatively, the nozzle heads can be placed in parallel (i.e., across the width of the substrate) to ensure that the adhesive is applied to the entire width of the substrate.

[0173] In a preferred embodiment, a negative pressure source or vacuum source (not shown) is arranged below the substrate 130, opposite to the sprayer 140, to increase the penetration depth and uniformity of the adhesive. The negative pressure source can be any suitable suction device that draws the adhesive through the substrate, such as a suction pump, etc.

[0174] In some embodiments, the substrate includes its own binder composition. In these embodiments, the binder may or may not be added to the substrate. In one such embodiment, the substrate comprises biocomponent fibers 600, wherein one of the components comprises an outer sheath 64 at least partially surrounding an inner core 62. In certain embodiments, the sheath 64 and the core 62 may be substantially concentric with each other ( Figure 5A In other embodiments, the core 84 may be non-concentric with the sheath 82 ( Figure 5C In other embodiments, the core 72 and the sheath 74 may be placed side by side with each other ( Figure 5B ). Of course, other configurations are also possible. For example, the core 184 can include shapes other than circular, such as dog-bone, square, triangle, diamond, etc. Optionally, the fiber 180 can include multiple cores, or it can be divided into three, four or more quadrants.

[0175] The sheath 64 may include a material that bonds to the nanoparticles. For example, the sheath 64 may include a material that becomes sticky and / or flows when heated and / or dried. During the heating / drying step, the sheath 64 portion of the fiber is heated to its melting point until it becomes sticky and / or flows to bond the nanoparticles to the substrate. In a preferred embodiment, bonding and drying are performed simultaneously in the drying device 160.

[0176] Fig.13 Schematically depicted is a fiberizing system 150 for converting a group of nanofibers into individual nanoparticles. As used herein, the term "fiberizing" means converting (e.g., opening, separating, isolating and / or individualizing) clusters, clumps, or other groups of nanoparticles that may or may not be entangled with one another into individual nanoparticles having at least one dimension less than 1 micron. Figures 14A-14C shows large clusters of entangled nanofibers ( Fig.14A ), small clusters of tangled nanofibers ( Fig. 14B ) and single nanoparticles ( Fig. 14C ) instance.

[0177] As shown, the fiberizing system 150 includes a feeder 200, such as a hopper, for feeding relatively large or large clusters / bundles of nanoparticles (see Fig.14A ) is introduced into the system 150. The feeder 200 may comprise any suitable hopper device known to those skilled in the art, and is preferably configured to introduce large clusters of particles into the process at a specified rate, which rate depends on the fiberization rate downstream. The nanoparticles may be introduced continuously at a specified rate, or at intervals of a specific rate. The bundled large clusters of nanoparticles may be broken up before being introduced into the feeder 200.

[0178] It should be appreciated that the nanoparticles can be introduced into the fiberizing device 150 in a variety of different forms. For example, raw nanofibers can be produced as long separate fibers. In this form, the nanofibers can be cut to obtain a desired length to diameter ratio.

[0179] The system 150 also includes a separator 210, such as a blender, for separating or breaking large clusters / bundles of nanoparticles into small clusters / agglomerates of nanoparticles (see Fig. 14B ). The feeder 200 delivers the nanofibers to the separator 210 in a stable and continuous state by any mechanical means. The delivery speed will depend on various factors, such as the speed of the substrate 130 along the feeder 120, the fiberization rate of the nanoparticles, etc. By controlling the amount of nanoparticles falling into the separator 210, the amount of nanoparticles dispersed into the substrate can be controlled, thereby achieving a continuous production process.

[0180] In one embodiment, the separator 210 includes a housing 212 having a first opening 214 coupled to the feeder 200 and a second opening 216 coupled to the downstream process. The size of the second opening 216 preferably allows only nanofiber clusters of a certain size to pass through. The separator 210 may include a plurality of rotatable blades (not shown) designed to rotate around a vertical axis within the housing 212 to separate and open the coarse nanofiber clusters. The blades may have the same or different pitches and cambers to allow the entangled fibers to be broken or "opened" sequentially from the first opening 214 to the second opening 216.

[0181] The fiberizing system 150 also includes an airflow (discussed in more detail below) throughout the system extending from the separator 210 to the nozzle 220. The airflow (along with a series of pumps discussed below) provides the motive force to move the nanofibers through the system 150. In one embodiment, the airflow is generated by an air compressor 230 configured to supply compressed air to the system, but it will be appreciated that other forms of gas may be used to convey the nanofibers through the system 150.

[0182] The system 150 includes one or more pumps for moving the nanofiber clusters and ultimately individual nanoparticles throughout the system. The pump may include any suitable pump, such as a positive displacement pump, a centrifugal pump, an axial flow pump, etc. In one embodiment, the first pump 240 includes a first inlet fluidly coupled to the air compressor 230 through a first channel 242 and a second inlet fluidly coupled to the separator 210 through a second channel 244. Compressed air is sucked into the first pump 240, which generates a negative pressure (e.g., a vacuum) to draw the nanofiber clusters from the separator 210 into the pump (discussed in more detail below). The system 150 may also include a second and third pumps 250, 260, each of which is fluidly coupled to the outlet of the first pump 240. Similarly, the second and third pumps 250, 260 generate a negative pressure to draw the nanofiber clusters through the third channel 252.

[0183] In certain embodiments, the pump 240 includes an ejector 300. Fig.15 As shown, the ejectors 300 each include a motive fluid inlet 302 and a nanofiber inlet 304, which are coupled to an outlet 306 through a fluid channel 308. The fluid channel 308 includes a converging inlet nozzle 310, a diffuser throat 312, and a diverging outlet diffuser 314. High-pressure, low-speed air is converted into low-pressure, high-speed air, thereby generating the pressure difference required for suction. Based on the Venturi effect and the Bernoulli principle, the primary fluid medium (e.g., compressed air) is used to generate a vacuum to draw the nanofibers into the ejector 300 and discharge them through the outlet 306. The diameter of the ejector 300 depends on the volume flow rate of the compressed air, the suction requirements, the pressure drop, and the fluid pressure of the compressed air.

[0184] review Fig.13 , the third channel 252 includes a joint 254 that divides the third channel 252 into two independent channels, each of which leads to the second pump and the third pump 250, 260. The joint 254 preferably includes a surface or wall substantially perpendicular to the third channel 252 to form a T-shaped intersection. The surface can be any surface that hinders the nanofibers from flowing through the channel, such as the inner wall of the channel at the connection point, or other inner walls with changes in direction, such as curved surfaces, vertical surfaces, etc. Optionally, the channel may include walls or other surfaces arranged in the channel or protruding into the channel in the fluid path. In one embodiment, the channel extends to a roughly T-shaped joint that includes two independent channels extending from the joint. The second ejector is configured to pull the nanofibers into the T-joint at a speed sufficient to break up at least some of the nanofibers.

[0185] As the nanofiber clusters move through the third channel 252, they are pushed toward the surface or wall due to the negative pressure applied by the second and third pumps 250, 260. The velocity of the nanofibers relative to the joint 254 creates collisions with sufficient kinetic energy to cause at least some of the nanofiber clusters to break into smaller nanofiber clusters and / or into individual nanoparticles having at least one size less than 1 micron.

[0186] To generate the kinetic energy required to break up the nanofiber clusters, air is propelled throughout the system 150 at a rate of about 500 feet per minute (fpm) to about 10,000 feet per minute, preferably about 2,000 fpm to about 6,000 fpm. The system 150 includes a sufficient amount of suction pressure, preferably at least about 20 psi. The suction pressure generates a total pressure of at least about 100 psi throughout the system.

[0187] In certain embodiments, the system 150 further includes fourth and fifth fluid channels 262, 264, which couple the outlets of the second and third pumps 250, 260 to the reactor 270. Fig.16 As shown, the reactor 270 includes a top surface 272, a bottom surface 274 and an inner annular chamber 276 extending from the top surface 272 to the bottom surface 274. The reactor 270 also includes a central tube 275 having an open upper inlet 278 and an outlet 280. The reactor 270 may also include one or more upper outlets 282. The reactor 270 may be coupled to an energy source (not shown) that is configured to generate a vortex of vortex gas in the annular chamber 276. The energy source may include any suitable energy source, such as a pump, a compressor, a generator, etc. The vortex gas preferably flows from the bottom of the reactor 270 around the central tube 275 to the top, so that the nanofiber clusters and individual nanoparticles move upward from the bottom surface 275 to the top surface 272.

[0188] In another embodiment, the generation of vortex does not require a separate energy source. In this embodiment, nanofiber clusters 290 and individual nanoparticles 292 enter the reactor 270 through bottom inlets 284, 285, 286, 287. The inlets 284, 285, 286, 287 are tilted upward to facilitate the movement of nanofibers and nanoparticles around the central tube 275. In a preferred embodiment, at least one or more of the inlets 284, 285, 286, 287 are tilted so that the nanofibers and nanoparticles are substantially tangential to the central tube 275 when entering the reactor 270. Once they enter the annular chamber 276, the velocity vectors (speed and direction) of the nanofibers and nanoparticles generate vortices within the reactor 270, causing them to swirl around the central tube 275 and reach the upper part of the chamber 276. The swirling gas preferably flows from the bottom of the reactor 270 around the central tube 275 to the top so that the nanofiber clusters and individual nanoparticles move upward from the bottom surface 275 to the top surface 272. The nanofibers 290 and nanoparticles 292 are blown from the bottom of the reactor to the top without any interference. The vortex in the chamber 276 can further break up (eg, open, separate and / or individualize) the nanofiber clusters 290 as they pass through the reactor 270.

[0189] In some embodiments, the reactor 270 may also be coupled to an energy source (not shown) configured to generate a vortex of swirling gas within the annular chamber 276. The energy source may include any suitable energy source, such as a pump, a compressor, a generator, and the like.

[0190] The system 100 may also include another pump or negative pressure source coupled to the upper outlet 282 (e.g., see Fig.17 ). The negative pressure draws the fibers out of the outlet 282, so that the fibers 290 leave the reactor 270. Since the individual nanoparticles 292 are significantly lighter than the entangled nanofibers 290 that are still gathered together, these individual nanoparticles 292 are sucked into the upper inlet 278 of the central tube 275. At the same time, the larger and heavier nanofiber clusters 290 that have not yet been broken are drawn out from the upper outlet 284. The upper outlet 284 can be coupled to other pumps (not shown), or to the first pump 240. In this way, the nanofiber clusters 290 are sent back into the process for further breaking, thereby forming a re-feed system to further break the remaining nanofiber clusters.

[0191] The outlet 280 of the central tube 275 is coupled to the nozzle 220 (see Fig.13). Individual nanoparticles 292 are drawn into nozzle 220 where they are dispersed onto the substrate surface or into the fiber stream (discussed below). Nozzle 220 may comprise any suitable nozzle known to those skilled in the art. In one embodiment, nozzle 220 has a plurality of outlets whose outer dimensions are tailored to the size (i.e., area) of the substrate passing under nozzle 220. Nozzle 220 will disperse the nanoparticles onto the substrate at a rate driven by the pressure of the entire system.

[0192] In certain embodiments, system 100 includes more than one nozzle coupled to outlet 280 of reactor 270. The nozzles can be arranged on the substrate in any suitable arrangement (eg, side-by-side, in series, in parallel, etc.).

[0193] It will be appreciated that pump 240 or pumps 250, 260 can feed the nanofiber / air mixture directly into nozzle 220 (i.e., bypassing reactor 270). In this embodiment, the pressure within the system is designed to generate sufficient kinetic energy to break or open substantially all of the nanofibers into individual nanoparticles, thereby eliminating the need for reactor 270 to separate the nanoparticles from larger fiber clusters.

[0194] Reference Fig.17 , another embodiment of a fiberizing system 320 will now be described. As shown, the fiberizing system 320 includes a separator 325 for separating larger or large nanofiber clusters passing through the system 320 into smaller nanofiber clusters. A first ejector 326 is coupled to the outlet of the separator 325 for drawing the nanofibers from the separator 325 into the system 320. An air compressor (not shown) is also coupled to the ejector 326 to provide a motive fluid, as described above.

[0195] Similar to the previous embodiments, the second and third ejectors 330, 340 are coupled to the outlet of the first ejector 326. The nanofibers are drawn from the first ejector 320 and pushed toward the surface of the T-junction 350 to break at least some of the nanofibers into smaller clusters or individual nanoparticles.

[0196] Each of the second and third ejectors 330, 340 has an outlet coupled to another T-junction 360, 370. As before, the nanofibers are pushed toward the surface of the T-junction 360, 370 to further break them up. The T-junction 360, 370 are each coupled to two fluid channels entering the bottom 380 of the reactor. Therefore, the bottom 380 of the reactor has four separate inlets 382, ​​384, 386, 388 for the passage of the nanofibers. Each of these inlets is preferably tilted upward and located at opposite corners of the reactor. This allows the nanofibers to enter the vortex of the reactor and then swirl upward to the upper portion 390 of the reactor.

[0197] As previously referenced Fig.16 Said, the reactor comprises an annular chamber, wherein the central tube has an open upper end and a lower end coupled to the nozzle. The nanofibers that have been fully broken into individual nanoparticles flow through the open upper end and enter the central tube for dispersion by the nozzle. The heavier nanoparticle clusters that have not yet been broken leave the reactor through one of four independent outlets 392, 394, 396, 398. Ejectors 410, 420 provide the power of extracting nanofibers from the reactor 400, as described above. The outlets 392, 394 are coupled to the ejector 410 by a T-shaped intersection 412, respectively, and the outlets 396, 398 are coupled to the ejector 420 by a T-shaped intersection 422, respectively. In this case, the nanofibers flow into one channel from two channels when passing through the intersections 412, 422.

[0198] The ejectors 410, 420 are each coupled to the T-junctions 430, 440. As previously described, the nanofibers are pushed into the T-junctions 430, 440 to further break them into individual nanoparticles. Then, the T-junctions 430, 440 are each coupled to the bottom 380 of the reactor 400 (through inlets 432, 434, 442, 444). This allows the nanofibers to return to the reactor 400 for further processing. This process is continued for each nanofiber cluster until it is completely broken into nanoparticles and enters the nozzle through the central tube. As a last step, the individualized nanofibers are sprayed from the nozzle onto any substrate or mixed with any fiber spinning stream. In this process, the suction is up to 20psi and the pressure is up to 100psi.

[0199] In certain embodiments, fibrosis system 150 may include a separate control system that monitors nanofibers to determine when they are broken into a single nanoparticle suitable for passing through a nozzle. The control system may, for example, simply monitor the pressure of the entire system to ensure that enough pressure is applied to the nanofibers to break them into nanoparticles. Alternatively, the control system may include various sensors arranged by the system to detect the characteristics of nanoparticles, such as weight or size. The sensor may be arranged in, for example, the reactor 400 so that the control system may control the various parameters of the reactor 400, such as the negative pressure applied to outlet 392,394,396,398, the speed of the eddy current of the annular chamber, or the pressure applied to the center tube that nanoparticles are sucked into the nozzle.

[0200] Fig.18Another embodiment of a system 500 for producing a multilayer nonwoven material is shown. As shown, the system 500 includes a first unwinder and a second unwinder 502, 504 and a single winder 506, and the winder 506 is used to wind up the first and second substrates 510, 512 downstream of the system 500. As in the previous embodiment, the system 500 may also include a support surface (not shown) for each substrate 510, 512. The first unwinder and the second unwinder 502, 504 are used to advance the first and second substrates 510, 512 into the process, where they are connected together and then wound up on the single winder 506, as described below.

[0201] The system 500 includes first and second spray guns 520, 522, each located downstream of the first and second unwinders 502, 504, for applying adhesive to the first and second substrates 510, 512. The system 500 also includes first and second fiberizing systems / devices 530, 532, which are located downstream of each spray gun 520, 522. As previously discussed, the fiberizing devices 530, 532 generate individual nanoparticles and disperse the nanoparticles onto the substrates 510, 512.

[0202] After the nanoparticles are dispersed into the substrates 510, 512, the two substrates are connected together at the connection point 540 so that they are advanced downstream together. The two substrates may be bonded to each other at this point, or they may simply be placed one on top of the other.

[0203] The system 500 also includes a heater / drying device, such as an IR oven 550, located downstream of the connection point 540 of the two substrates. The heating / drying device heats and dries the two substrates to bond them to each other and to bond the nanoparticles to the fibers within the substrates. The substrates can, for example, be laminated to each other.

[0204] In certain embodiments, nanoparticles are dispersed in two substrates 510, 512. In such an embodiment, system 500 is designed so that nanoparticles are dispersed by the first surface of each substrate. Then, substrates can be connected together so that the first surface faces each other. Alternatively, the first surface can be opposite to each other (that is, substrate is connected at the second relative surface of each substrate). In another embodiment again, the first surface of the first substrate is connected to the second surface of the second substrate.

[0205] Fig.19A filtration product 700 is shown, comprising a filter medium 710 of a nonwoven material, comprising fibers 722 and nanoparticles 720 dispersed in at least a portion of the filter medium 710. As shown, the filter medium 710 has a first upper surface 712 and a second lower surface 714. The nanoparticles have been dispersed through the upper surface 712 so that they extend beyond the upper surface 712 and into the filter medium 710 to a certain depth, as described above. The filtration product 700 also includes a support layer 730, which can be any suitable support layer known in the art, such as a substantially rigid polymer that provides support for the filter medium 710, or an open membrane having a plurality of pores for gas or fluid to pass through (as described above).

[0206] Fig. 20 Another filtration product 740 is shown that includes a filter media 710 of a nonwoven material including fibers 722 and nanoparticles 720 dispersed in a portion of the filter media 710. In this embodiment, the product 740 includes a scrim layer 750 bonded to a support layer 730.

[0207] Fig.21 A dual layer filtration product 760 is shown, which includes a first filter medium and a second filter medium 762, 764 bonded to each other. As shown, nanoparticles 720 have been dispersed deep within each filter medium 762, 764. In this embodiment, the nanoparticles 720 have been dispersed through the inner surfaces 766, 768 of the filter media 762, 764. In another embodiment (not shown), the nanoparticles are dispersed through the outer surfaces 770, 772 of the filter media 762, 764. In yet another embodiment, the nanoparticles 720 can be deposited on the inner surface 766 of the medium 762 and the outer surface 772 of the medium 764.

[0208] In yet another aspect, the system for producing fiber-making material comprises the first device for generating one or more fiber streams and the second device for isolating nanoparticles in the gaseous medium. The second device is dispersed into the nanoparticles in the stream and the stream is fed into the fiber stream to form fibrous material. The system may also include a dispersing device, for example a nozzle, which is coupled to the second device and is configured to feed the nanoparticles substantially uniformly into the fiber stream. The fiber stream can be generated with any suitable mechanism known in the art (for example melt-blown, spunbond or spunlace, thermal bonding, combing, air-laid, wet-laid, extruded, co-molded, acupuncture, stitching, hydraulic entanglement, etc.).

[0209] In one example, the system can include a spunbond line, in which filaments are formed by spinning molten polymer and stretching the molten filaments. The fiber bundles of the filaments are separated and spread, and then layered on a net to form a web. The fibers are bonded in the form of sheets by thermal bonding and embossing. The first stream 630 can be introduced, for example, before the attenuation zone or before the bonding (consolidation) process.

[0210] In another embodiment, the system can include two carding machines arranged in series with each other. The first stream 630 can be introduced at any point after the first carding line and before the second carding line, so that the nanoparticles are sandwiched between the two carded fiber webs. Afterwards, all fibers (including the nanoparticles) are bonded together in a hot air bonding oven (the nanoparticles are thermally interlocked).

[0211] Fig. 22 Another embodiment for generating one or more fiber streams is shown. In this embodiment, nanoparticles are dispersed between two meltblowing dies where molten polymer is pushed through small holes to make fibers. When the nanoparticles encounter the fibers while they are still sticky, they mechanically entangle with the fibers and thermally bond to the fibers. Therefore, in some embodiments, no additional bonding process is required.

[0212] like Fig. 22 As shown, the apparatus 600 for forming a fibrous structure comprises a fiberizing system 610 similar to one of the above-described systems and devices. The fiberizing system 610 comprises a nozzle 620 or similar device for dispersing individual nanoparticles into a first stream 630. The apparatus 600 also comprises a system for generating one or more fiber streams that will be combined with the individual nanoparticle stream 630. The system may comprise any system known in the art, such as spunbonding, carding, and extrusion, among others.

[0213] In another embodiment, the equipment comprises a first feeder and a second feeder, such as a hopper 640, 642, which is coupled to a first extruder and a second extruder 650, 652. For example, each extruder may comprise an extrusion screw (not shown) driven by a conventional drive motor (not shown). When polymer is advanced through extruders 650, 652, polymer is gradually heated to a molten state due to the drive motor rotating the extrusion screw. Thermoplastic polymers are heated to a molten state and can be completed in a plurality of discrete steps, when they advance to two melt-blown dies 660, 662 by discrete heating zones of extruders 650, 652 respectively, their temperature gradually increases. Melt-blown dies 660, 662 can be another heating zone, in which the temperature of the thermoplastic resin is maintained at a higher level to extrude.

[0214] Each meltblowing die 660, 662 is configured so that the two attenuating air streams of each die converge to form a single air stream that entrains and attenuates the molten strands as they flow from the small holes or orifices 672 in the meltblowing die. The molten strands 20 are attenuated into fibers or, depending on the degree of attenuation, into microfibers, which have a relatively small diameter, typically smaller than the diameter of the orifices 672. Thus, each meltblowing die 660, 662 has a corresponding single primary air stream 680, 690 containing entrained and attenuated polymer fibers.

[0215] The main gas streams 680, 690 containing polymer fibers are aligned to converge at the forming zone 700. In addition, a first stream 630 of individual nanoparticles is added to the two main gas streams 680, 690 of thermoplastic polymer fibers or microfibers at the forming zone 30. The introduction of the individual nanoparticles into the two main gas streams 680, 690 of fibers is intended to produce a distribution of secondary fibrous materials 32 in the combined main gas streams 680, 690 of fibers. This can be achieved by merging the first stream 630 of individual nanofibers between the two main gas streams 680, 690 so that all three gas streams converge in a controlled manner.

[0216] Examples of suitable meltblowing dies that can be used to produce nonwoven materials are discussed in more detail in U.S. Patent Nos. 6,972,104, 8017534, and 7772456, and U.S. Patent Application No. US20200216979A1, the complete disclosures of which are incorporated herein by reference in their entirety for all purposes.

[0217] Example 1

[0218] A microfiber substrate of bicomponent fibers having an inner circular portion of polyester and an outer concentric portion of HDPE is provided in the form of a roll. In a roll-to-roll process, the substrate is sprayed with an adhesive and nanofibers or nanoparticles of biosoluble glass fibers are deposited. The nonwoven product is then heated in an oven and the cooled nonwoven product is collected onto another roll.

[0219] Nanoparticles are based on the following Figure 12-16 The process described in was deposited. In the experiments, biosoluble glass nanofibers were used. The nanofiber diameter was about 700 nanometers and the length was about 500 micrometers. In the following examples, a carded hot air bonded nonwoven made of bicomponent fibers was used as the substrate:

[0220] Flat sheet filter media samples were tested at a filtration velocity of 110 fpm. Sample size was 12" x 12". NaCl salt particles ranging from 0.3 to 10 microns were used as the contaminant.

[0221] Example 2

[0222] A carded nonwoven made of 3 denier PET / PE bicomponent fibers was used as the substrate. A composition comprising water, 2-hexyloxyethanol, isopropanolamine, sodium dodecylbenzene sulfonate, lauramine oxide, and ammonium hydroxide was used as the binder. Different nanofiber addition amounts were controlled by adjusting the line speed.

[0223] Table 1

[0224]

[0225]

[0226] This example shows that by controlling the amount of nanoparticles added, the MERV rating can be increased from MERV 7 to MERV 13.

[0227] Example 3

[0228] A high loft hot air bonded carded nonwoven with 5 denier bicomponent fibers was used as the substrate. A typical starch adhesive was diluted and sprayed before nanofiber deposition. The starch fully bonded the nanofibers as the solvent evaporated and dried under an IR heater.

[0229] Table 2

[0230]

[0231] Example 4

[0232] Use spunbond or meltblown media as a substrate, wherein nanoparticles are incorporated into the substrate after IPA discharge, as described herein. Spunbond fibers are made of a molten polymer that is spun and stretched to produce filaments. The average basis weight of the substrate is about 90gsm, and the average thickness is about 0.57mm. Use a base sample without any nanoparticles incorporated. Prepare 4 separate samples, which include nanoparticles incorporated into the substrate, as described herein. In sample 2, nanoparticles are incorporated into meltblown fibers after IPA discharge. In samples 1, 3, and 4, nanoparticles are incorporated into spunbond fibers after IPA discharge. The test results are shown in Table 3 below.

[0233] Table 3

[0234] sample# Substrate PD E1 E2 E3 MERV 1 CAB81(Spunbond) 0.41 96% 100% 100% 16 2 CAB81(meltblown) 0.24 75% 98% 100% 14 3 CAB81(Spunbond) 0.40 92% 100% 100% 15 4 CAB81(Spunbond) 0.17 48% 87% 99% 12 Base CAB81(Spunbond) 0.07 9% 46% 90% 9

[0235] As shown, in all three particle groups, the efficiency of the filter media samples incorporating nanoparticles was higher than that of the base samples, and the efficiency of the E2 and E3 particle groups was significantly improved. The overall MERV rating of the samples increased from MERV 7 (base sample) to MERV 12 to MERV 16 (using nanoparticles). The pressure drop of the base sample without nanoparticles was 0.07 inches of water column. The pressure drop of samples 1-4 increased slightly, ranging from 0.17 to 0.41 inches of water column. In sample 2, where nanoparticles were incorporated into meltblown fibers, the MERV rating was 14 and the pressure drop was 0.24 inches of water column.

[0236] Example 5

[0237] A 5 denier hot through bonded carded fiber was used as the substrate. A base sample without nanoparticles incorporated was used. Two separate samples were prepared that included nanoparticles incorporated into the substrate as described herein. The test results are shown in Table 4 below.

[0238] Table 4

[0239]

[0240] As shown, in all three particle groups, the efficiency of the filter media samples incorporating nanoparticles increased significantly compared to the base samples. The overall MERV rating of the samples increased from MERV 6 (base sample) to MERV 13 (with nanoparticles). The pressure drop of the base sample without nanoparticles was 0.03 inches of water column. The pressure drop of samples 1 and 2 increased slightly, ranging from 0.31 to 0.33 inches of water column.

[0241] Example 6

[0242] Meltblown fibers were used as substrates. The average basis weight of the substrate was about 24 gsm and the average thickness was about 0.4 mm. A base sample without nanoparticles or adhesives (e.g., PVOH) was used. Sample 1 included meltblown fibers with the tape side facing up. PVOH was sprayed on the fibers, but nanoparticles were not incorporated. Sample 2 included meltblown fibers with the velvet side facing up. PVOH was sprayed on the fibers, but nanoparticles were not incorporated. Sample 3 included meltblown fibers with PVOH sprayed thereon, and nanoparticles were incorporated into the fibers, as described herein. The test results are shown in Table 5 below.

[0243] Table 5

[0244] sample# Substrate PD E1 E2 E3 MERV Base Meltblown 0.35 82% 96% 99% 14 1 Meltblown 0.38 68% 88% 93% 13 2 Meltblown 0.41 78% 95% 97% 14 3 Meltblown 1.02 92% 99% 99% 15

[0245] As shown, in all three particle groups, especially in the E1 particle group, the efficiency of sample 3 incorporating nanoparticles increased compared to the other three base samples. The overall MERV rating of sample 3 increased from MERV 13 or 14 (base samples) to MERV 15 (using nanoparticles). The PVOH added to samples 2 and 3 did not significantly increase the pressure drop (i.e., 0.35 for the base sample, 0.38 and 0.41 for samples 1 and 2). The pressure drop of sample 3 did increase from about 0.40 inches of water column to about 1 inch of water column. In sample 3, incorporating nanoparticles into the meltblown fiber, the MERV rating was 15 and the pressure drop was 1.02 inches of water column.

[0246] Example 7

[0247] 5 denier hot through bonded carded fibers were used as the substrate. A base sample without nanoparticles was used. Seven additional samples were prepared, which included 5 denier carded fibers with nanoparticles incorporated into the substrate, as described herein. The test results are shown in Table 6 below.

[0248] Table 6

[0249]

[0250] As shown, the seven samples incorporating nanoparticles had higher efficiencies than the base samples in all three particle groups, especially in the E2 and E3 particle groups. The overall MERV rating increased from MERV 6 (base sample) to MERV 7 to MERV 13 (with nanoparticles). The pressure drop only increased from 0.03 inches of water column to a maximum of 0.32 inches of water column.

[0251] Example 8

[0252] High loft spunbond fibers were used as substrates in a continuous fiber production line. This test included two different versions: 205-6 and 205-2, where the settings on the continuous fiber production line were changed to produce two substrates with different weights and thicknesses. Each version (205-6 and 205-2) used a base sample without nanoparticles incorporated. Six additional samples were prepared that included 205-6 and 205-2 fibers and nanoparticles incorporated into the substrate, as described herein. The test results are shown in Table 7 below.

[0253] Table 7

[0254] sample# Substrate PD E1 E2 E3 MERV Base 205-6 0.04 0% 9% 43% 6 Base 205-2 0.04 0% 8% 37% 6 1 205-6 0.86 88% 98% 99% 15 2 205-2 0.48 79% 96% 99% 14 3 205-6 0.87 82% 97% 99% 14 4 205-2 0.42 61% 90% 98% 13 5 205-6 0.78 79% 97% 99% 14 6 205-2 0.23 44% 79% 96% 11

[0255] As shown, in all three particle groups, the efficiency of the six samples incorporating nanoparticles increased significantly compared to the base samples. The overall MERV rating increased from MERV 6 (base samples) to MERV 11 to MERV 14 (with nanoparticles). The pressure drop only increased from 0.04 inches of water column to a maximum of 0.87 inches of water column. The pressure drop in the 205-2 sample only increased to a maximum of 0.48 inches of water column.

[0256] Example 9

[0257] Spunbond and meltblown fibers were used as substrates. The average basis weight of the substrate of the spunbond fibers was about 70 gsm, and the average basis weight of the substrate of the meltblown fibers was about 24 gsm. The average thickness of the substrate was about 0.75 mm. A base sample without nanoparticles was used. Five additional samples were prepared, including spunbond and meltblown fibers and nanoparticles incorporated into the fibers, as described herein. In samples 1-3, nanoparticles were sprayed onto meltblown fibers. In samples 4 and 5, nanoparticles were sprayed onto spunbond fibers. In addition, in samples 1 and 2, the adhesive PVOH was not sprayed onto the substrate. PVOH was sprayed onto samples 3-5. The test results are shown in Table 8 below.

[0258] Table 8

[0259] sample# Substrate PD E1 E2 E3 MERV Base Spunbond+MB 0.07 2% 17% 29% 5 1 Spunbond+MB 0.41 100% 100% 100% 16 2 Spunbond+MB 0.56 100% 100% 100% 16 3 Spunbond+MB 0.26 99% 100% 100% 16 4 Spunbond+MB 0.4 100% 100% 100% 16 5 Spunbond+MB 0.17 97% 100% 100% 16

[0260] As shown, in all three particle groups, the efficiency of the five samples incorporating nanoparticles was significantly improved compared to the base samples. The overall MERV rating increased from MERV 5 (base samples) to MERV 16 (with nanoparticles). The pressure drop only increased from 0.07 inches of water column to a maximum of 0.56 inches of water column. In samples 3-5 (PVOH sprayed onto the substrate), the pressure drop only increased to a maximum of 0.4 inches of water column.

[0261] Example 10

[0262] 5 denier hot air bonded carded glass fiber was used as the substrate. A base sample without nanoparticles was used. Three additional samples were prepared, which included 5 denier carded glass fibers and nanoparticles incorporated therein. The test results are shown in Table 9 below.

[0263] Table 9

[0264]

[0265] As shown, in all three particle groups, the efficiency of the three samples incorporating nanoparticles increased significantly compared to the base samples. The overall MERV rating increased from MERV 6 (base samples) to MERV 12 or MERV 13 (with nanoparticles). The pressure drop only increased from 0.03 inches of water column to a maximum of 0.27 inches of water column.

[0266] Embodiment 11

[0267] A fiber blend of 5 denier and 7 denier hot air bonded combed glass fibers was used as the substrate. The medium was hot air bonded. A base sample without nanoparticles was used. Nineteen additional samples were prepared, which included a fiber blend of 5 denier and 7 denier combed glass fibers and nanoparticles incorporated therein. The test results are shown in Table 10 below.

[0268] Table 10

[0269]

[0270]

[0271] As shown, in all three particle groups, all 19 samples incorporating nanoparticles showed significant improvements in efficiency compared to the base samples. The overall MERV rating increased from MERV 6 (base samples) to MERV 10 to MERV 13 (with nanoparticles) (most samples were rated MERV 13). The pressure drop only increased from 0.03 inches of water column to a maximum of 0.31 inches of water column.

[0272] Although these devices, systems and methods have been described in detail herein according to certain preferred embodiments, many modifications and changes may be made thereto by those skilled in the art. Therefore, the foregoing description should not be interpreted as being limited thereto, but rather should be interpreted as including the aforementioned obvious changes, and only limited by the spirit and scope of the following claims.

[0273] For example, in a first aspect, the first embodiment is a method for producing a fibrous material. The method includes providing a fibrous substrate having a first surface and a second surface opposite the first surface, dispersing a binder into the substrate between the first surface and the second surface, and dispersing nanoparticles through the first surface of the substrate so that the nanoparticles are retained at least between the first surface and the second surface of the substrate, wherein at least one dimension of a single nanoparticle is less than 1 micron.

[0274] A second embodiment is the first embodiment, further comprising spraying the substrate with the adhesive such that the adhesive penetrates the first surface to an interior structure of the substrate.

[0275] A third embodiment is any combination of the first two embodiments, wherein the adhesive is disposed from the first surface to the second surface of the substrate.

[0276] The fourth embodiment is any combination of the first three embodiments, further comprising applying negative pressure to the second surface of the substrate.

[0277] The fifth embodiment is any combination of the first five embodiments, wherein the adhesive comprises a material selected from the group consisting of starch and adhesives.

[0278] The sixth embodiment is any combination of the first five embodiments, wherein the adhesive comprises a binder selected from the group consisting of starch, dextrin, guar gum, PVOH and synthetic resins.

[0279] The seventh embodiment is any combination of the first six embodiments, wherein the adhesive is a polymer adhesive.

[0280] The eighth embodiment is any combination of the first seven embodiments, wherein the adhesive comprises a material selected from the group consisting of dextrin and PVOH.

[0281] The ninth embodiment is any combination of the first eight embodiments, wherein the adhesive is a solution, emulsion, suspension, hot melt, curable, neat and / or a combination.

[0282] The tenth embodiment is any combination of the first nine embodiments, further comprising controlling the amount of binder applied to the fibers.

[0283] An eleventh embodiment is any combination of the preceding ten embodiments, further comprising spraying the adhesive through one or more openings of the nozzle.

[0284] A twelfth embodiment is any combination of the first eleven embodiments, further comprising dip coating the adhesive onto the substrate.

[0285] A thirteenth embodiment is any combination of the first twelve embodiments, further comprising generating adhesive droplets having a size of about 20 to 30 microns.

[0286] A fourteenth embodiment is any combination of the previous thirteen embodiments, further comprising cross-linking the adhesive.

[0287] A fifteenth embodiment is any combination of the previous fourteen embodiments, further comprising applying energy to the adhesive to crosslink the adhesive.

[0288] A sixteenth embodiment is any combination of the first fifteen embodiments, further comprising mixing a surfactant with the binder.

[0289] A seventeenth embodiment is any combination of the previous sixteen embodiments, further comprising coating the fibers of the substrate with a second adhesive after the nanoparticles have been dispersed into the substrate.

[0290] The 18th embodiment is any combination of the previous 17 embodiments, further comprising separating or isolating the nanoparticles within a gaseous medium and dispersing the nanoparticles into the first surface of the substrate such that individual nanoparticles penetrate and pass through the first surface of the substrate into the depth of the substrate.

[0291] A 19th embodiment is any combination of the previous 18 embodiments, wherein the gaseous medium is compressed air.

[0292] The 20th embodiment is any combination of the previous 19 embodiments, further comprising isolating the nanoparticles in a liquid medium and dispersing the nanoparticles into the first surface of the substrate such that the nanoparticles penetrate and pass through the first surface of the substrate into the depth of the substrate.

[0293] A twenty-first embodiment is any combination of the previous twenty embodiments, further comprising heating the fiber material to bond the nanoparticles to the fibers within the matrix.

[0294] In a second aspect, a first embodiment is a method for producing a fibrous material. The method includes providing a fibrous substrate having a first surface and a second surface opposite the first surface, wherein the fibers include a bonding composition, and dispersing nanoparticles through the first surface of the substrate such that the nanoparticles are bonded to the bonding composition at least between the first surface and the second surface, wherein at least one dimension of the nanoparticles is less than 1 micron.

[0295] A second embodiment is the first embodiment, further comprising applying negative pressure to the second surface of the substrate.

[0296] A third embodiment is any combination of the first two embodiments, wherein the fiber comprises a biocomponent fiber having a sheath and a core.

[0297] A fourth embodiment is any combination of the first three embodiments, wherein the core and sheath are non-concentric.

[0298] A fifth embodiment is any combination of the first four embodiments, further comprising heating the sheath to bond the nanoparticles to the substrate.

[0299] The sixth embodiment is any combination of the first five embodiments, further comprising isolating the nanoparticles in a gaseous medium and dispersing the nanoparticles into the first surface of the substrate such that the nanoparticles penetrate and pass through the first surface of the substrate into the depth of the substrate.

[0300] The seventh embodiment is any combination of the first six embodiments, further comprising isolating the nanoparticles in a liquid medium and dispersing the nanoparticles into the first surface of the substrate such that the nanoparticles penetrate and pass through the first surface of the substrate and into the depth of the substrate.

[0301] In a third aspect, a first embodiment is a system for producing a fibrous material. The system comprises a feeder for advancing a fibrous substrate from an upstream end to a downstream end; a first device for distributing a binder onto the substrate to coat at least a portion of the fibers with the binder; and a second device for distributing nanoparticles through a first surface of the substrate such that the nanoparticles are disposed in the substrate between the first and second surfaces, wherein at least one dimension of the nanoparticles is less than 1 micron.

[0302] A second embodiment is the first embodiment, wherein the first device is a sprayer configured to dispense the adhesive such that the adhesive penetrates the first surface of the substrate to an internal structure of the substrate.

[0303] A third embodiment is any combination of the first two embodiments, wherein the adhesive is disposed from a first surface of the substrate to a second surface opposite the first surface.

[0304] A fourth embodiment is any combination of the first three embodiments, further comprising an energy source configured to apply negative pressure to the second surface of the substrate.

[0305] The fifth embodiment is any combination of the first four embodiments, wherein the adhesive comprises a binder selected from the group consisting of starch, dextrin, guar gum, PVOH and synthetic resins.

[0306] A sixth embodiment is any combination of the first five embodiments, wherein the adhesive comprises a tackifier selected from the group consisting of dextrin and PVOH.

[0307] The seventh embodiment is any combination of the first six embodiments, wherein the adhesive is a solution, emulsion, suspension, hot melt, curable, neat and / or a combination.

[0308] An eighth embodiment is any combination of the first seven embodiments, wherein the binder comprises a surfactant.

[0309] The ninth embodiment is any combination of the first eight embodiments, wherein the adhesive is a polymer adhesive.

[0310] The tenth embodiment is any combination of the first nine embodiments, further comprising an energy source arranged to apply energy to the substrate, wherein the energy is sufficient to crosslink the adhesive.

[0311] An eleventh embodiment is any combination of the preceding ten embodiments, wherein the first device comprises a nozzle having one or more openings configured to form the adhesive into droplets having a size of about 20 to 30 microns.

[0312] A twelfth embodiment is any combination of the first eleven embodiments, further comprising a third means for coating the fibers with a second adhesive.

[0313] A 13th embodiment is any combination of the first 12 embodiments, wherein the feeder comprises an upstream end and a downstream end, wherein the third device is disposed between the second device and the downstream end, and wherein the first device is disposed between the second device and the upstream end.

[0314] A fourteenth embodiment is any combination of the previous thirteen embodiments, further comprising a fiberizing device coupled to the second device for separating or isolating the nanoparticles in a fluid medium.

[0315] A fifteenth embodiment is any combination of the previous fourteen embodiments, wherein the nanoparticles are disposed within the gas in the fiberizing device.

[0316] A sixteenth embodiment is any combination of the preceding fifteen embodiments, wherein the nanoparticles are disposed within a liquid in the fiberizing device.

[0317] A seventeenth embodiment is any combination of the previous sixteen embodiments, further comprising a dryer disposed near the feeder between the second device and the downstream end for heating the nanoparticles and fibers.

[0318] The eighteenth embodiment is a fibrous material formed by any combination of the previous seventeen embodiments.

[0319] The 19th embodiment is a filter medium formed by any combination of the previous 17 embodiments.

Claims

1. A method for producing a fiber material, the method comprising: providing a substrate of fibers having a first surface and a second surface opposite the first surface; dispensing an adhesive into the substrate between the first surface and the second surface; as well as Nanoparticles are dispersed across the first surface of the substrate such that the nanoparticles are retained between at least the first surface and the second surface of the substrate, wherein at least one dimension of an individual nanoparticle is less than 1 micron.

2. The method of claim 1, further comprising spraying the substrate with the adhesive so that the adhesive penetrates the first surface of the substrate to its internal structure.

3. The method of claim 2, wherein the adhesive is dispersed from the first surface to the second surface of the substrate. The method of claim 1 , further comprising applying negative pressure to the second surface of the substrate.

5. The method of claim 1, wherein the binder comprises a material selected from the group consisting of starch and adhesives.

6. The method of claim 1, wherein the adhesive comprises a tackifier selected from the group consisting of starch, dextrin, guar gum, PVOH, and synthetic resins.

7. The method of claim 1, wherein the binder is a polymer adhesive.

8. The method of claim 1, wherein the adhesive comprises a material selected from the group consisting of dextrin and PVOH.

9. The method of claim 1, wherein the adhesive is a solution, emulsion, suspension, hot melt, curable, neat, and / or a combination.

10. The method of claim 1, further comprising controlling the amount of binder applied to the fibers.

11. The method of claim 1 , further comprising spraying the adhesive through one or more openings of a nozzle.

12. The method of claim 1 further comprising dip coating the adhesive onto the substrate.

13. The method of claim 1, further comprising generating adhesive droplets having a size of about 20 to 30 microns.

14. The method of claim 6, further comprising cross-linking the adhesive.

15. The method of claim 14, further comprising applying energy to the adhesive to cross-link the adhesive.

16. The method of claim 1, further comprising mixing a surfactant with the adhesive.

17. The method of claim 1, further comprising coating fibers of the substrate with a second adhesive after the nanoparticles have been dispersed into the substrate.

18. The method of claim 1, further comprising separating or isolating the nanoparticles within a gaseous medium and dispersing the nanoparticles into the first surface of the substrate such that the individual nanoparticles pass through the first surface of the substrate into the depth of the substrate.

19. The method of claim 18, wherein the gaseous medium is compressed air.

20. The method of claim 1, further comprising isolating the nanoparticles in a liquid medium and dispersing the nanoparticles into the first surface of the substrate such that the nanoparticles penetrate through the first surface of the substrate into a depth of the substrate.

21. The method of claim 1, further comprising heating the fiber material to bond the nanoparticles to fibers within the substrate.

22. A method for producing a fibrous material, the method comprising: providing a substrate of fibers having a first surface and a second surface opposite the first surface, wherein the fibers include a bonding composition; as well as Nanoparticles are dispersed across the first surface of the substrate such that the nanoparticles are bonded to the adhesive composition at least between the first surface and the second surface, wherein at least one dimension of the nanoparticles is less than 1 micrometer.

23. The method of claim 22, further comprising applying negative pressure to the second surface of the substrate.

24. The method of claim 22, wherein the fiber comprises a biocomponent fiber having a sheath and a core.

25. The method of claim 24, wherein the core and the sheath are non-concentric.

26. The method of claim 24, further comprising heating the sheath to bond the nanoparticles to the substrate.

27. The method of claim 22, further comprising isolating nanoparticles in a gaseous medium and dispersing the nanoparticles into the first surface of the substrate such that the nanoparticles pass through the first surface of the substrate and penetrate deep into the substrate.

28. The method of claim 22, further comprising isolating nanoparticles in a liquid medium and dispersing the nanoparticles into the first surface of the substrate such that the nanoparticles penetrate through the first surface of the substrate and penetrate deep into the substrate.

29. A system for producing a fibrous material, the system comprising: a feeder for advancing a substrate of fibers from an upstream end to a downstream end; a first device for dispensing a binder onto said substrate to coat at least a portion of said fibers with said binder; and A second device for dispersing nanoparticles across the first surface of the substrate such that the nanoparticles are disposed in the substrate between the first surface and the second surface, wherein at least one dimension of the nanoparticles is less than 1 micron.

30. The system of claim 29, wherein the first device is a sprayer configured to dispense the adhesive such that the adhesive penetrates the first surface of the substrate to an internal structure of the substrate.

31. The system of claim 30, wherein the adhesive is disposed from a first surface of the substrate to a second surface opposite the first surface.

32. The system of claim 31, further comprising an energy source configured to apply negative pressure to the second surface of the substrate.

33. The system of claim 29, wherein the adhesive comprises a tackifier selected from the group consisting of starch, dextrin, guar gum, PVOH, and synthetic resins.

34. The system of claim 29, wherein the adhesive comprises a tackifier selected from the group consisting of dextrin and PVOH.

35. The system of claim 29, wherein the adhesive is a solution, emulsion, suspension, hot melt, curable, neat, and / or a combination.

36. The system of claim 29, wherein the adhesive comprises a surfactant.

37. The system of claim 29, wherein the adhesive is a polymer adhesive.

38. The system of claim 29, further comprising an energy source arranged to apply energy to the substrate, wherein the energy is sufficient to crosslink the adhesive.

39. The system of claim 29, wherein the first device comprises a nozzle having one or more openings configured to form the adhesive into droplets having a size of about 20 to 30 microns.

40. The system of claim 29, further comprising a third means for coating the fibers with a second adhesive.

41. The system of claim 40, wherein the feeder comprises an upstream end and a downstream end, wherein the third device is disposed between the second device and the downstream end, and wherein the first device is disposed between the second device and the upstream end.

42. The system of claim 29, further comprising a fiberizing device coupled to the second device for separating or isolating the nanoparticles in a fluid medium.

43. The system of claim 42, wherein the nanoparticles are disposed within a gas in the fiberizing device.

44. The system of claim 42, wherein the nanoparticles are disposed within a liquid in the fiberizing device.

45. The system of claim 29, further comprising a dryer disposed near the feeder between the second device and the downstream end for heating the nanoparticles and the fibers.

46. ​​A fibrous material formed by the method of claim 1.

47. A filter medium formed by the method of claim 1.

Citation Information

Patent Citations

  • Multilayer filter medium for filter, method for producing the same, and air filter

    US10252201B2

  • Durable nanofiber synthetic filter media

    US10799820B2

  • Integrated nanofiber filter media

    US20090266759A1

  • Wind turbine

    US20200040941A1

  • Multi-die melt blowing system for forming co-mingled structures and method thereof

    US20200216979A1